Optical article with interference coating with color robustness
By introducing an outermost sheet of refractive index gradient into the interference multilayer coating of the optical product, the problem of unstable reflective performance caused by changes in the thickness of the interference coating in the prior art is solved, and better optical characteristics and aesthetic appearance are achieved while maintaining mechanical and thermal properties.
Patent Information
- Application Number
- CN202411825465.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-14
- Filing Date
- 2024-12-12
- Publication Date
- 2025-06-17
AI Technical Summary
The interference coatings of existing optical products are prone to thickness changes during the manufacturing process, resulting in unstable reflective performance and uneven aesthetic appearance, affecting its mechanical and thermal properties.
An interference multilayer coating with a low refractive index layer less than 1.55 and a high refractive index layer equal to or greater than 1.55 is used, and a refractive index gradient is introduced into the outermost sheet layer to ensure that the refractive index gradually decreases in the direction away from the base element.
It achieves good anti-reflection or reflection characteristics in the visible light zone and UV band, while improving the robustness and aesthetic appearance of the optical product, maintaining mechanical and thermal properties.
Smart Images

Figure BDA0005184147280000091 
Figure BDA0005184147280000371 
Figure BDA0005184147280000381
Abstract
Description
Technical Field
[0001] The present invention relates to an optical article comprising a base element having a front main surface and a rear main surface, such as a substrate, at least one of the two main surfaces being coated with an interference multilayer coating. The interference multilayer coating is specific and is capable of and / or configured to provide both good optical and colorimetric characteristics without sacrificing its mechanical and thermal properties. The optical article may in particular be an ophthalmic lens, especially an eyeglass lens.
[0002] The present invention also relates to a method for manufacturing such an optical article. Background Art
[0003] Interference coatings generally consist of multiple layers including interference thin layers, which are typically an alternation of layers of dielectric materials based on high refractive index (such as mineral oxides) and layers of dielectric materials based on low refractive index, deposited for example under vacuum.
[0004] Interference coatings can be reflective coatings or anti-reflective coatings.
[0005] Reflective coatings are generally designed to give the surface of the optical article they coat an average light reflectance coefficient Rv (front OA) in the visible light region of strictly more than 2.5% for an angle of incidence of 15°. Reflective coatings are generally applied to the surface of an optical article in order to provide a reduction in the transmission of visible, ultraviolet or infrared light (i.e.: an increase in light reflection). They can also give the optical article a mirrored and / or colored appearance, which may be desirable for aesthetic purposes. For example, such coatings are used to provide sunglasses lenses with a mirrored effect.
[0006] Conversely, when deposited on a transparent substrate, the function of an anti-reflection coating is to reduce its light reflection and thus increase its light transmission. The substrate thus coated will therefore have an increased transmission / reflection light ratio, thereby improving the visibility of the object placed behind it. When seeking to obtain the maximum anti-reflection effect, it is preferred to provide this type of coating on both faces (front and back) of the substrate. This anti-reflection coating is commonly used in the ophthalmic field. Accordingly, traditional anti-reflection coatings are designed and optimized to reduce reflection in the visible light region (typically in the spectral range of 380 nm to 780 nm) on the lens surface. Generally, the average light reflection coefficient Rv in the visible light region on the front and / or back of a standard ophthalmic lens is between 1.5% and 2.5%. Some of these anti-reflection coatings can also be designed and optimized to reduce reflection in the UVA band of 315 nm to 380 nm and / or the UVB band of 280 nm to 315 nm on the lens surface. These UVA and UVB bands are indeed particularly harmful to the retina. For traditional anti-reflection lenses, the average reflection in the UVA and UVB regions can thus reach high levels (up to 60%). On the one hand, regarding non-solar anti-reflection articles sold by most manufacturers in recent years, for an incident angle of 30° to 45°, the average UV reflection ranges from 10% to 25%. This is not a problem for the front of the lens because the main part of the UV radiation coming from the front of the wearer and possibly reaching the wearer's eyes (normal incidence, 0° to 15°) is usually absorbed by the ophthalmic lens substrate. On the other hand, if the lens does not have an anti-reflection coating effective in the ultraviolet region, the UV radiation generated by a light source located behind the wearer may be reflected on the back of the lens and reach the wearer's eyes, thereby potentially affecting the wearer's health. This phenomenon is made more evident by the trend for fashion sunglasses to have large diameters, which increases the risk of stray reflections entering the eyes. It should be recognized that the light that may be reflected onto the back of the lens and reach the wearer's eyes has a narrow range of incident angles.
[0007] There are numerous patents relating to methods for manufacturing interference coatings, such as anti-reflection coatings, which are effective at least in the visible light region and have satisfactory mechanical properties.
[0008] For example, document JP 2001 / 288562 describes a method for improving the adhesion between a substrate (i.e., a glass plate) and a multilayer, especially for window glass used in architectural and automotive applications. This document describes a method for coating a substrate with a thin film of a silicon compound by irradiating an evaporated silicon material with arc discharge plasma in a film-forming apparatus. The method further includes introducing a gas flow composed of a mixture of oxygen and nitrogen, wherein the introduced gas ratio of oxygen to nitrogen, i.e., N2 / (N2+O2), increases from 0 to 1.0 in order to increase the refractive index of the silicon compound thin film thus formed. In the illustrated example, the substrate is coated with: an antireflection coating of 80 nm, which has a continuously increasing refractive index gradient ranging from 1.48 (corresponding to pure SiO2 obtained with 100% O2) to 2.1 (corresponding to pure silicon nitride obtained with 100% N2) (the levels of the gas ratio N2 / (N2+O2) are 0, 0.2, 0.4, 0.5, 0.8, and 1, respectively), and a 20-nm pure SiO2 layer, obtained with 100% O2 and thus having a stable refractive index of 1.48. The reflectance at a specific wavelength of 550 nm is mentioned as 0.5%, while for the glass plate, the reflectance is 4%. However, this document does not mention the average light reflectance coefficient Rv in the entire visible light region ranging from 380 nm to 780 nm. This document also discloses that there is no significant visible damage for this example after a wear test (i.e., Taber wear test (load 250 gf, rotation speed 100 times), equivalent to the abrasion resistance test specified in JIS-R3221).
[0009] However, it is desirable to improve the robustness and aesthetic appearance of an optical article (such as a lens) without degrading its mechanical properties. It is well known that an antireflection coating having an outermost layer with a low refractive index layer can be designed to exhibit a low Rv. However, this outermost low refractive index layer may generally cause deterioration of the mechanical properties of the antireflection coating.
[0010] In the present invention, the "robustness" of an interference coating is defined as the ability of this interference coating to tolerate variations, regardless of the variations caused by its manufacturing process. For example, these variations depend on the type of substrate used, the settings of the manufacturing machine (temperature profile, appropriate time, electron gun settings...), and / or its usage mode, and the replacement of the manufacturing machine with another one.
[0011] In fact, when manufacturing a multilayer antireflection coating on an industrial scale, some thickness variations usually occur in each layer. These variations result in different reflection performances, and especially different residual reflection colors of the multilayer antireflection coating perceived. If the residual reflection colors of the antireflection coatings of two lenses perceived are different, these lenses will appear different and will not be able to be paired and associated.
[0012] In addition, depending on the curvature of the lens and the incident value (angle θ), the residual reflection color of the multilayer anti-reflection coating of each lens appears non-uniform in color on all surfaces of the lens ("chameleon effect"). The observer can see different residual reflection colors between the right and left parts of the lens according to the incident angle θ, such as a color gradient of different hues "h" (not the same color, e.g., changing from blue to red) or a color gradient of different color intensities (e.g., changing from a saturated color to a less saturated color, or vice versa). Therefore, it would be desirable to improve the aesthetic appearance of such lenses by, for example, obtaining a perceived uniform residual reflection color of the lens surface for an observer viewing the lens wearer.
[0013] Robustness is also necessary for lenses with a mirror coating (i.e., a reflective coating) commonly used for sunglasses. In fact, for a mirror coating (as well as for an anti-reflection coating), the variability of the color perceived from one lens to another can be problematic, especially in a pair of glasses (such as sunglasses) where two separate lenses are placed adjacent to each other.
[0014] Therefore, the object of the present invention is thus to propose a new type of optical article which at least partially avoids the above-mentioned drawbacks.
[0015] In fact, there is still a need to provide novel interference coatings which have very good anti-reflection properties at least in the visible light region and possibly in the UVA and UVB bands for anti-reflection coatings or very good reflection properties for mirror coatings, while preferably having robustness properties and an aesthetic appearance simultaneously compared to interference coatings of the prior art.
[0016] In addition, there is also a need to provide an interference coating for an optical article (such as an ophthalmic lens), the optical article preferably having a perceived predetermined color reproducible on a production line.
[0017] There is also a need to provide novel interference coatings which particularly have additional mechanical properties and thermal properties. Summary of the Invention
[0018] The applicant has sought to develop a new type of transparent optical article which includes an organic or mineral base element, preferably a lens, and more preferably an ophthalmic lens for glasses, with an interference multilayer coating, the interference coating having, in particular, advantageously improved optical characteristics and colorimetric characteristics compared to known interference-coated optical articles, while having very good mechanical properties and thermal properties.
[0019] For this purpose, the applicant has developed a new and atypical structure for an optical article which includes an interference multilayer coating.
[0020] The present invention relates to an optical article which at least includes:
[0021] A basic element having a front main surface and a rear main surface,
[0022] At least one interference multilayer coating deposited on the front main surface and / or the rear main surface of the substrate and comprising at least one layer having a low refractive index of less than 1.55 defined as a "LI layer" and at least one layer having a high refractive index of equal to or greater than 1.55 defined as a "HI layer", the refractive index being expressed at a wavelength of 550 nm at 25 °C,
[0023] Characterized in that:
[0024] - The interference multilayer coating comprises an outermost layer that exhibits a refractive index gradient that gradually decreases in a direction away from the basic element and has a maximum refractive index of less than or equal to 1.55.
[0025] The Applicant has found that such a specific outermost layer enables the interference multilayer coating obtained to have very good antireflection properties for at least the visible light region and possibly in the UVA and UVB bands for an antireflection coating, or very good reflection properties for a mirror coating, while in particular having robustness properties and an aesthetic appearance.
[0026] In fact, generally, the interference multilayer coating has, in reflection,
[0027] A chromaticity C* defined in the International Colorimetry CIE L*a*b* (1976), the standard deviation thereof defined as "σC*" being strictly less than 2.0 for an incident angle of 15°, and having a hue angle defined in the International Colorimetry CIE L*a*b* (1976), the standard deviation thereof defined as "σh" being less than or equal to 15° for an incident angle of 15°, provided that the interference multilayer coating has an average light reflection coefficient Rv in the visible light region of less than or equal to 2.5% for an incident angle of 15°, or
[0028] A chromaticity C*, the standard deviation thereof defined as "σC*" being strictly less than 6.9 for an incident angle of 15°, and having a hue angle, the standard deviation thereof defined as "σh" being less than or equal to 5.8° for an incident angle of 15°, provided that the interference multilayer coating has an average light reflection coefficient Rv in the visible light region strictly greater than 2.5% for an incident angle of 15°.
[0029] As used herein, the standard deviation of the colorimetric and optical characteristics refers to the average value of each of these characteristics on 500 samples obtained after applying a ±2.2% random variation to the thickness of each layer of the interference multilayer coating, all layers varying independently and simultaneously.
[0030] In fact, due to these features, the interference multilayer coatings (anti-reflection coatings or mirror coatings) according to the invention allow for excellent color robustness, which is particularly crucial for mass production and the aesthetic appearance of the residual reflection color pairing of left and right lenses (especially glasses). In fact and as mentioned above, the manufacturer must ensure the reproducibility of this residual reflection color of such interference multilayer coatings so that the colors perceived from one lens to another are substantially the same, in order to enable the pairing of lens colors, that is, two lenses produced by the same industrial process cannot be distinguished from each other, and the observer considers their residual reflection colors to be the same.
[0031] Here, an improvement of at least 0.1% in σC and / or σh between standard optical articles commercially available on the market and the novel optical articles according to the invention is significant (i.e., better colorimetric robustness in mass production). Detailed Description
[0032] A) Definition
[0033] The terms "comprise" (and any of its grammatical variants such as "comprises" and "comprising"), "have" (and any of its grammatical variants such as "has" and "having"), "contain" (and any of its grammatical variants such as "contains" and "containing"), and "include" (and any of its grammatical variants such as "includes" and "including") are open-ended linking verbs. They are used to specify the presence of the stated features, wholes, steps, or components or groups thereof, but do not preclude the presence or addition of one or more other features, wholes, steps, or components or groups thereof. Thus, a method or a step in a method that "comprises", "has", "contains", or "includes" one or more steps or elements has those one or more steps or elements, but is not limited to having only those one or more steps or elements.
[0034] Unless otherwise indicated, all numerical values or expressions regarding amounts of ingredients, ranges, reaction conditions, etc. used herein should be understood to be modified in all instances by the term "about".
[0035] Likewise, unless otherwise indicated, an indication of an interval of values "from X to Y" or "between X and Y" according to the invention means including the values X and Y.
[0036] We mean ophthalmic articles defined by, but not limited to, the following: corrective lenses, non-corrective lenses, contact lenses, intraocular lenses, magnifying lenses, protective lenses, and goggles containing photochromic compounds in a coating, lens material, film, or any adjacent layer.
[0037] As used herein, "substrate element" may include an optical (e.g., ophthalmic) substrate or an optically quality support film (i.e., laminate) secured to the optical / ophthalmic substrate by an adhesive (e.g., an optically quality pressure sensitive adhesive (PSA layer)).
[0038] As used herein, "interference coating" means a coating that generally consists of interference thin layers and includes at least one layer having a low refractive index defined as an "LI layer" with a refractive index less than 1.55, and at least one layer having a high refractive index defined as an "HI layer" with a refractive index equal to or greater than 1.55.
[0039] In this application, when an optical lens includes one or more coatings on its surface, the expression "depositing a layer, sheet, or coating onto an article" is intended to mean depositing the layer, sheet, or coating onto the outer (exposed) surface of the outer coating of the article, that is, the coating that is farthest from the substrate.
[0040] Unless otherwise specified, a coating, layer, or sheet referred to as being "on" or deposited "onto" a substrate / substrate element is defined as a coating, layer, or sheet that (i) is located above the substrate / substrate element, (ii) does not necessarily contact the substrate / substrate element, that is, one or more intermediate coatings / sheets may be disposed between the substrate / substrate element and the coating or sheet in question, and (iii) does not necessarily completely cover the substrate / substrate element.
[0041] In a preferred embodiment, a coating on or deposited onto a substrate / substrate element is in direct contact with this substrate.
[0042] When "layer / sheet 1 is located below layer 2 / sheet 2", it is intended to mean that layer 2 / sheet 2 is farther from the substrate than layer 1 / sheet 1, respectively.
[0043] The outermost layer or sheet of an interference coating means the layer or sheet of the interference coating that is farthest from the substrate.
[0044] The innermost layer or sheet of an interference coating means the layer or sheet of the interference coating that is closest to the substrate.
[0045] The inner layer / sheet of an interference coating means any layer / sheet of the interference coating other than the outermost layer / sheet of the interference coating.
[0046] Moreover, unless otherwise stated, all thicknesses disclosed in this application relate to physical thicknesses.
[0047] As used herein, a layer of an interference coating is defined as having a thickness greater than or equal to 1 nm. Thus, when counting the number of layers in a reflective coating, any layer with a thickness less than 1 nm will not be considered. When counting the number of layers in an interference coating, sub-layers (which typically have a physical thickness of 150 nm) are also not considered.
[0048] Unless otherwise indicated, the refractive indices mentioned in this application are expressed at a wavelength of 550 nm at 25 °C.
[0049] As used herein, the rear (or inner or concave or CC) surface of the base element / substrate is intended to mean the surface that is closest to the wearer's eye when the article is in use. The rear surface is typically concave. In contrast, the front (or convex or CX) surface of the substrate / base element is the surface that is farthest from the wearer's eye when the article is in use. The front surface is typically convex.
[0050] Moreover, as used herein, a "transparent substrate / base element" should be understood to be transparent when no significant loss of contrast is perceived when observing an image through the substrate, i.e., when an image is formed through the substrate without adversely affecting the quality of the image.
[0051] The colorimetric coefficients (such as chroma C* and hue "h") of the optical article of the present invention in the International Colorimetric System CIE L*a*b* (1976) are calculated between 380 nm and 780 nm, taking into account the standard light source D 65 and the observer (angle 10°). The observer is the "standard observer" as defined in the International Colorimetric System CIE L*a*b*. In fact, in the CIE L*a*b* space, not only can the overall change in color be represented, but also the changes related to one or more of the parameters L*, a*, and b* can be represented. This can be used to define new parameters and relate them to visual attributes. The clarity related to luminance is directly represented by the value of L*. Chroma: C* = (a* 2 + b* 2 ) 1 / 2 defines the chroma. Hue angle: h = tg-1(b* / a*) (expressed in degrees); related to the hue.
[0052] According to the present invention, colorimetric measurements (reflection) of the surface (convex / front) coated with the interference multi-layer coating of the present invention are performed using a Zeiss spectrophotometer: the reflection coefficient Rv, the hue angle h, and the chroma C* in the International Colorimetric CIE (L*, a*, b*) space, taking into account the standard light source D65 and the standard observer 10° (for h and C*). They are provided for an incident angle of 15° or 35°.
[0053] According to the present invention, the "angle of incidence (symbol θ)" is the angle formed by a ray of light incident on the surface of an ophthalmic lens and the normal to the surface at the point of incidence. The ray of light is, for example, a luminous light source such as the standard light source D65 as defined in the International Colorimetric CIE L*a*b* (1976). Generally, the angle of incidence varies from 0° (normal incidence) to 90° (grazing incidence). The general range of the angle of incidence is from 0° to 75°, and is typically 15° for the present invention.
[0054] The optical characteristic includes at least the average light reflectance coefficient R in the visible light region v , also referred to as the "light reflectivity".
[0055] In this text, the "light reflectivity", denoted as R v , is defined as in the standard ISO 13666:1998 and is measured according to ISO 8980-4, that is, it is the weighted spectral reflectance average over the entire visible spectrum between 380 nm and 780 nm. R v is typically measured for an angle of incidence of less than 17°, typically 15°, but can be evaluated for any angle of incidence.
[0056] According to the present invention, when the average light reflectance coefficient Rv in the visible light region on the front principal surface and / or the rear principal surface of the optical article is strictly greater than 2.5%, more preferably greater than 3%, and even more preferably greater than 5%, this means that the multilayer interference coating can provide specular behavior on the front principal surface or the rear principal surface of the optical article respectively. In particular, the "specular behavior" enables a reduction in the transmission of visible light, ultraviolet light, and / or infrared light. In other words, an optical article having specular behavior on its front principal surface reflects at least a part of the light reaching said surface. The specular behavior increases the light reflection at the article / air interface in a determined part of the spectrum. The reflection can be in the ultraviolet spectrum or in the visible spectrum or in the infrared spectrum.
[0057] According to the present invention, when the average light reflectance coefficient Rv in the visible light region on the front principal surface and / or the rear principal surface of the optical article is equal to or less than 2.5%, this means that the multilayer interference coating can provide antireflection behavior on the front principal surface and / or the rear principal surface of the optical article respectively.
[0058] According to the present invention, the average reflectance coefficient R UV is defined by the following relationship:
[0059]
[0060] where R(λ) represents the spectral reflectance coefficient of the optical article at a given wavelength, and W(λ) represents a weighting function equal to the product of the solar spectral irradiance Es(λ) and the efficiency relative spectral function S(λ).
[0061] The spectral function W(λ) enabling the calculation of the ultraviolet radiation transmittance coefficient is defined according to the ISO 13666:1998 standard. This enables the expression of the ultraviolet solar radiation distribution adjusted by the relative spectral efficiency of such radiation for the user, since both the solar spectral energy Es(λ) (such as less overall emission of UVB rays compared to UVA rays) and the spectral efficiency S(λ) (UVB rays are more harmful than UVA rays) are considered simultaneously. The values of these three functions in the ultraviolet region are given in the table disclosed in the ISO 13666:1998 standard (the said table is reproduced on page 6 of the publication WO 2012 / 076714).
[0062] In the present application, the average reflectance coefficient Ruv is measured at an incident angle of 35°. Examples of the calculation of Ruv at incident angles of 30° and 45° are given in WO 2012 / 076714. A person skilled in the art can easily implement the calculation based on the measured reflectance values on the corresponding surfaces at the desired incident angles (0°, 15°, 35°).
[0063] As previously mentioned, in the present invention, the "robustness" of an optical article (such as an ophthalmic lens) is defined as the ability of this lens to tolerate variations, regardless of the variations caused by its manufacturing process. For example, these variations depend on the type of substrate / base element used, the settings of the manufacturing machine (temperature profile, appropriate time, electron gun settings...), and / or its usage mode, and the replacement of the said manufacturing machine by another one.
[0064] According to the present invention, the robustness of various parameters is calculated using the Essential MacLeod software provided by Thin Film Center Inc. Simulations are carried out to test the robustness (also known as the standard deviation or Std Dev) of the interference multilayer coatings according to the present invention. 500 iterations are carried out to evaluate the influence of the thickness variations caused by the manufacturing process (one standard deviation corresponds to a ±2.2% variation of the normal / Gaussian distribution of the thickness of each layer of the stack, all of which vary independently and simultaneously), and these thickness variations may affect the performance and characteristics of two different lenses including the same structure (same composition and thickness of layers), such as chromaticity C*, hue "h" (reflection), and optical coefficients: Rv, Ruv for an incident angle of 15° (light source D65 and observer 10°). The "average" values given below are the averages of the parameters of 500 samples obtained after applying a ±2.2% random variation to the thickness of each layer of the stack. The standard deviation quantifies the amount of variation or dispersion of a set of data values. A low standard deviation indicates that the data points tend to be close to the average value of the parameter.
[0065] In the context of the present invention, the ESPF ("Eye Sun Protection Factor") of an optical article is given by the following relationship:
[0066] ESPF = 100% / (Ruv 35° (%) + 3σRuv 35° (%))
[0067] wherein,
[0068] Ruv 35° is the amount of UV (between 280 nm and 380 nm) reflected from the back surface at an incident angle of 35°,
[0069] 3σRuv 35° (%) is three times the robust value of Ruv 35 .
[0070] B) Optical article according to the invention
[0071] As described above, the present applicant has developed a transparent optical article, in particular an ophthalmic lens, such as an eyeglass lens, the transparent optical article comprising a base element, such as a substrate of mineral or organic glass, the base element comprising at least an interference multi-layer coating, the transparent optical article having improved color and optical robustness and doing so without compromising the mechanical and thermal properties, its aesthetic appearance of the optical article, and also without compromising the economic and / or industrial feasibility of its manufacture.
[0072] The optical article is as defined in a set of claims and comprises a base element having a front principal surface and a rear principal surface and at least one interference multi-layer coating deposited on the front principal surface and / or the rear principal surface of the substrate.
[0073] B.1 Base element / substrate
[0074] The optical article according to the invention comprises a base element.
[0075] According to one embodiment, the base element may be a laminate, that is, an optically quality support film fixed to an optical / ophthalmic substrate due to an adhesive, such as an optically quality pressure-sensitive adhesive (PSA layer). Preferably, the support film is made of cellulose triacetate (TAC) and has a thickness of at least 40 microns, preferably a thickness in the range of 40 μm to 300 μm (including the end values) and preferably a thickness of 80 μm to 190 μm. The material of the support film may be selected from the group of films made of: cellulose triacetate (TAC), cellulose acetate butyrate (CAB), polycarbonate (PC), poly(ethylene terephthalate) (PET), poly(methyl methacrylate) (PMMA), urethane polymer (TPU), cycloolefin copolymer (COC), polyester block copolyamide (such as Pebax), and polyimide.
[0076] According to another embodiment (described below), the base element may comprise an ophthalmic substrate of a transparent optical article, such as a lens or a lens blank, and more preferably an ophthalmic lens or a lens blank.
[0077] Generally, the interference coating of the optical article according to the present invention can be deposited on any substrate, and preferably on an organic lens substrate (such as a thermoplastic or thermosetting plastic material).
[0078] The thermoplastic can be selected from, for example: polyamide; polyimide; polysulfone; polycarbonate and its copolymers; poly(ethylene terephthalate) and poly(methyl methacrylate) (PMMA).
[0079] The thermosetting material can be selected from, for example: cycloolefin copolymers, such as ethylene / norbornene or ethylene / cyclopentadiene copolymers; homopolymers and copolymers of allyl carbonates of straight-chain or branched aliphatic or aromatic polyols, such as the homopolymer of diethylene glycol bis(allyl carbonate) (CR );homopolymers and copolymers of (meth)acrylic acid and its esters that can be derived from bisphenol A; polymers and copolymers of thio(meth)acrylic acid and its esters, polymers and copolymers that can be derived from bisphenol A or phthalic acid and allyl aromatic compounds such as allyl esters of styrene, polymers and copolymers of urethane and thiourethane, polymers and copolymers of epoxy resins, and polymers and copolymers of sulfides, disulfides and episulfides, and combinations thereof.
[0080] As used herein, (co)polymer is intended to mean copolymer or polymer. As used herein, (meth)acrylate is intended to mean acrylate or methacrylate. As used herein, polycarbonate (PC) is intended to mean homopolycarbonate or copolymerized polycarbonate and block copolymerized polycarbonate.
[0081] Preferably, a homopolymer of diethylene glycol bis(allyl carbonate) (CR ), an allyl and (meth)acrylic acid copolymer having a refractive index between 1.54 and 1.58, a polymer and copolymer of ethyl thiocarbamate, a polycarbonate.
[0082] In particular, the substrate recommended for the base element of the present invention is a substrate selected from materials obtained by (co)polymerization of bis(ethylene glycol) bis(allyl carbonate) and may correspond to ESSILOR lenses.
[0083] As will be shown below, before depositing the antireflection coating of the present invention, the substrate / base element may be coated with one or more functional coatings. These functional coatings conventionally used in optical devices may be but are not limited to an impact-resistant primer layer, an abrasion-resistant coating and / or a scratch-resistant coating, a polarization coating, a photochromic coating or a coloring coating. Hereinafter, the substrate means a bare substrate or such a coated substrate.
[0084] Preferably, the substrate / base element and the optional abrasion-resistant coating and / or scratch-resistant coating usually applied to the substrate have a similar / close refractive index in order to avoid streaks or appearance defects.
[0085] Before depositing the interference coating, the surface of the substrate is usually subjected to physical or chemical surface activation treatment in order to enhance the adhesion of the antireflection coating. This pretreatment is usually carried out under vacuum. It may be bombardment with high-energy and / or reactive substances such as with an ion beam (“ion pre-cleaning” or “IPC”) or with an electron beam, corona discharge treatment, ion spallation treatment, ultraviolet radiation treatment or plasma-mediated treatment under vacuum (usually using oxygen or argon plasma). It may also be an acidic or alkaline treatment and / or a solvent-based treatment (water, hydrogen peroxide or any organic solvent).
[0086] B.2 Interference multi-layer coating
[0087] As previously mentioned, the interference (IF) coating according to the present invention has been designed to not only provide excellent color robustness, but also preferably provide low reflection in the visible light region (380 nm to 780 nm) and advantageously in the UV band (280 nm to 380 nm), while having good mechanical properties. In fact, due to its characteristics, the interference coating according to the present invention has a suitable aesthetic appearance (i.e.: good colorimetric robustness) and preferably also has suitable optical characteristics, such as very low reflection in both the visible light region and in the UV band and excellent optical robustness.
[0088] For these purposes, an interference multilayer coating (hereinafter referred to as "IF coating") is characterized by various optical and colorimetric parameters that enable these objectives to be achieved.
[0089] According to the invention, the IF coating presents a specific stack of the following:
[0090] - at least one layer having a low refractive index of less than 1.55, defined as a "LI layer",
[0091] - at least one layer having a high refractive index of equal to or greater than 1.55, defined as a "HI layer", and
[0092] - the outermost sheet layer, which exhibits a refractive index gradient that gradually decreases in the direction away from the base element and has a maximum refractive index of less than 1.55.
[0093] Thus, this outermost sheet layer has a low refractive index that gradually decreases in the direction away from the base element.
[0094] In particular, the outermost sheet layer has a maximum refractive index of less than or equal to 1.52, preferably less than or equal to 1.48, and typically less than or equal to 1.47. As used herein, "a maximum refractive index of less than or equal to 1.55" includes the following values and / or any interval between these values: 1.55, 1.54, 1.53, 1.52, 1.51, 1.50, 1.49, 1.48, 1.47, 1.46, 1.45, 1.44, 1.43, 1.42, 1.41, etc.
[0095] In particular, this outermost sheet layer that exhibits a refractive index gradient is deposited by electron beam evaporation of at least one precursor compound in the presence of oxygen introduced into a vacuum chamber, and the flow rate of oxygen is gradually increased during the deposition of the outermost sheet layer. Generally, the at least one precursor is SiO2. According to an embodiment, this outermost sheet layer also contains SiO2 in its structure. The applicant has indeed found that when the oxygen flow rate increases, the refractive index of the as-deposited precursor material (such as SiO2) becomes lower and lower. Without being bound by any theory, it seems that this phenomenon can be explained as follows: as the oxygen flow rate increases, the working pressure in the vacuum chamber increases, and thus the density of the as-deposited SiO2 film decreases due to the loss of kinetic energy of the deposited material, which is caused by an increase in collisions with residual gaseous molecules. This fact can be used to produce a gradually decreasing refractive index in the outermost sheet layer of an antireflection coating.
[0096] The Applicant has indeed found that by replacing the standard outermost LI layer of a conventional IF coating with an LI outermost layer exhibiting a refractive index gradient that gradually decreases in a direction away from the substrate element and having a maximum refractive index of less than 1.55, the thus-formed IF coating exhibits better colorimetric robustness (σh and σC*) than the said conventional IF coating. Additionally and as will be shown in the following examples, an IF coating according to the invention comprising this particular LI outermost layer generally also exhibits lower Rv and σRv, lower Rv and σRuv, and higher ESPF (considering 3 times σRuv) than the corresponding conventional IF coating, the conventional IF coating having a uniform outermost layer typically consisting of SiO2 and thus having a stable and regular refractive index. Furthermore, the Applicant has found that an IF coating according to the invention has mechanical and thermal properties as good as those of these conventional IF coatings.
[0097] First of all, generally, the said IF coating has excellent color robustness in reflection. For interference coatings, especially in the field of ophthalmic lenses, good colorimetric robustness is crucial, particularly for mass production and the aesthetic appearance of the IF color matching of left and right lenses.
[0098] In fact, preferably, an IF coating according to the invention has a very low standard deviation of chromaticity C* and a standard deviation of hue "h". This means that the IF coating has a strong ability to withstand variations, regardless of the variations caused by its manufacturing process. As mentioned above, hue and chromaticity C* are defined in the International Colorimetry CIE L*a*b* (1976).
[0099] According to an embodiment, the IF coating is an antireflection coating, hereinafter referred to as an AR coating (i.e.: for an incident angle of 15°, Rv is less than or equal to 2.5%) and has the following characteristics.
[0100] According to this embodiment, the AR coating in particular has such a chromaticity C* that the standard deviation of chromaticity defined as "σC*" is strictly less than 2.0 for an incident angle of 15°.
[0101] In particular, the AR coating has a σC* of less than or equal to 1.9, preferably less than or equal to 1.8, typically less than or equal to 1.7 in reflection for an incident angle of 15°. As used herein, "the standard deviation of chromaticity defined as "σC*" is strictly less than 2.0" includes the following values and / or includes any interval between these values (including the limiting values other than 2.0): 1.99, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, etc.
[0102] Typically, an AR coating can have a chroma C* greater than or equal to 5, preferably greater than or equal to 6, particularly greater than or equal to 7 and typically greater than or equal to 8 for an incident angle of 15° in reflection. As used herein, "chroma C* greater than or equal to 5" includes the following values and / or any interval between these values (including the limiting values): 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, etc.
[0103] According to the present invention, the AR coating also has excellent hue robustness. In fact, the IF coating particularly has such a hue angle that the standard deviation defined as "σh" is less than or equal to 15°, preferably less than or equal to 12° for an incident angle of 15°. According to the present invention, "the standard deviation defined as "σh" is less than or equal to 15° for an incident angle of 15°" includes the following values and / or any interval between these values (in °): 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1, etc.
[0104] According to another embodiment, the IF coating is a reflective coating or a mirror coating, hereinafter referred to as "M" coating (i.e., for an incident angle of 15°, Rv is strictly greater than 2.5%), and has the following characteristics.
[0105] According to this embodiment, the M coating typically has a chroma C*, and the standard deviation of the chroma defined as "σC*" is strictly less than 6.9 for an incident angle of 15°.
[0106] In particular, the M coating has a σC* less than or equal to 6.9, preferably less than or equal to 6.8 and typically less than or equal to 6.7 for an incident angle of 15° in reflection. As used herein, "the standard deviation of the chroma defined as "σC*" is less than or equal to 6.9" includes the following values and / or any interval between these values (including the limiting values except 2.0): 6.9, 6.8, 6.7, 6.6, 6.5, 6.4, 6.3, 6.2, 6.1, 6.0, 5.9, 5.8, 5.7, 5.6, 5.5, etc.
[0107] Typically, the M coating can have a chroma C* greater than or equal to 20, preferably greater than or equal to 30, particularly greater than or equal to 40 and typically greater than or equal to 60 for an incident angle of 15° in reflection. As used herein, "chroma C* greater than or equal to 20" includes the following values and / or any interval between these values (including the limiting values): 20, 30, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, etc.
[0108] According to the present invention, the M coating also has excellent hue robustness. In fact, the IF coating has such a hue angle that the standard deviation defined as "σh" is particularly less than or equal to 5.7°, preferably less than or equal to 5.6°, for an incident angle of 15°. According to the present invention, "the standard deviation defined as 'σh' is less than or equal to 5.7° for an incident angle of 15°" includes the following values and / or any interval (in °) included between these values: 5.7, 5.6, 5.5, 5.4, 5.3, 5.2, 5.1, 5.0, 4.9, 4.8, 4.7, 4.6, 4.5, 4.0, 3.5, 3.5, 3.0, 2.5, 2.0, 1.5, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1, etc.
[0109] Regardless of which embodiment, the IF coating can be prepared without being limited by its hue angle h (0° to 360°), and the hue angle is related to the residual color exhibited by the IF coating.
[0110] In some embodiments, the IF coating has a hue angle (h) in the range of 15° to 120°, preferably 25° to 110°, thus resulting in a residual reflection color that is perceived as brown.
[0111] In particular, in some embodiments, the IF coating has a hue angle (h) in the range of 61° to 105°, thereby corresponding to a "yellow" residual reflection color.
[0112] In some embodiments, the IF coating has a hue angle (h) greater than or equal to 120°, more preferably greater than or equal to 130° and preferably in the range of 130° to 200°, thus producing an IF coating with a green residual reflection color. In particular, in some embodiments, the IF coating has a hue angle (h) in the range of 106° to 209°, thereby corresponding to a "green" residual reflection color.
[0113] In some embodiments, the IF coating has a hue angle (h) in the range of 200° to 300°, preferably 250° to 280°, thus resulting in a residual reflection color that is perceived as blue. In particular, in some embodiments, the IF coating has a hue angle (h) in the range of 210° to 330°, thereby corresponding to "blue" and derivative residual reflection colors, including more "blue - purple" or even "purple" residual reflection colors.
[0114] In some embodiments, the IF coating has a hue angle (h) in the range of 331° to 60°, thereby corresponding to "red" and derivative residual reflection colors, including "orange", "pink" or "pink gold" residual reflection colors.
[0115] Then, the IF coating according to the present invention preferably has excellent optical characteristics.
[0116] In particular, according to an embodiment where the IF coating is an AR coating, it has the following characteristics.
[0117] In particular, the AR coating has low reflection in the visible light region ranging from 380 nm to 780 nm for an incident angle of 15°. In particular, the AR coating has an average light reflection coefficient R in the visible light region of less than or equal to 2.5%, preferably less than or equal to 2.0%, particularly less than or equal to 1.5%, and typically less than or equal to 1.0%. v .
[0118] As used herein, "an average light reflection coefficient R in the visible light region of less than or equal to 2.5%" v includes the following values and / or any interval between these values (in %): 2.5, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.4, 0.3, 0.2, 0.1, etc.
[0119] Furthermore, the AR coating according to the present invention not only has very low reflection in the visible light region, but also has excellent optical robustness of this average light reflection coefficient Rv. In fact, the AR coating according to the present invention generally has an average light reflection coefficient Rv in the visible light region, and the standard deviation of the average light reflection coefficient defined as "σRv" is less than or equal to 0.10%, preferably less than or equal to 0.09%, particularly less than or equal to 0.08%.
[0120] According to the present invention, "the standard deviation defined as 'σRv' is less than or equal to 0.10%" includes the following values and / or any interval between these values (in %): 0.10, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1, 0.05.
[0121] In addition, the AR coating according to the present invention is configured to preferably also provide very low reflection in the UV band, and this has very good robustness.
[0122] Therefore, generally, the AR coating has an average reflection coefficient Ruv in the wavelength range of 280 nm to 380 nm of less than or equal to 5%, preferably less than or equal to 3.0%, particularly less than or equal to 2.5%, and typically less than or equal to 2.1%.
[0123] As used herein, "average reflection coefficient Ruv less than or equal to 5.0%" includes the following values and / or any interval (in %) between these values: 5.0, 4.9, 4.8, 4.7, 4.6, 4.5, 4.4, 4.3, 4.2, 4.1, 4.0, 3.9, 3.8, 3.7, 3.6, 3.5, 3.4, 3.3, 3.2, 3.1, 3.0, 2.9, 2.8, 2.7, 2.6, 2.5, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.4, 0.3, 0.2, 0.1, etc.
[0124] In addition, the AR coating has an average reflection coefficient Ruv for an incident angle of 35°, and the standard deviation of the average reflection coefficient, defined as "σRuv", is less than or equal to 0.50%, preferably less than or equal to 0.45%, and particularly less than or equal to 0.40%.
[0125] Moreover, as used herein, "standard deviation defined as 'σRuv' less than or equal to 0.50%" includes the following values and / or any interval (in %) between these values: 0.50, 0.45, 0.40, 0.35, 0.30, 0.25, 0.20, 0.15, 0.10, 0.05, etc.
[0126] Additionally, according to other embodiments where the IF coating is an M coating, it has the following optical characteristics.
[0127] In particular, the M coating has a relatively high reflection in the visible light region ranging from 380 nm to 780 nm for an incident angle of 15°. Specifically, the M coating has an average light reflection coefficient Rv in the visible light region that is strictly greater than 2.5%, preferably greater than or equal to 2.8%, particularly greater than or equal to 3.0%, and typically greater than or equal to 3.10%.
[0128] As used herein, "average light reflection coefficient Rv in the visible light region strictly greater than 2.5%" includes the following values and / or any interval (in %) between these values: 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.5, 5.0, 5.5, 6.0, etc.
[0129] In addition, the M coating according to the present invention not only has a very high reflectance in the visible light region but also has excellent optical robustness with respect to this average light reflectance coefficient Rv. In fact, the M coating according to the present invention generally has an average light reflectance coefficient Rv in the visible light region, and the standard deviation of the average light reflectance coefficient, defined as "σRv", is less than or equal to 1.0%, preferably less than or equal to 0.85%, and particularly less than or equal to 0.83%.
[0130] According to the present invention, "the standard deviation defined as 'σRv' being less than or equal to 1.0%" includes the following values and / or any interval between these values (in %): 1.0, 0.99, 0.98, 0.97, 0.96, 0.95, 0.94, 0.93, 0.92, 0.91, 0.90, 0.89, 0.88, 0.87, 0.86, 0.85, 0.84, 0.83, 0.82, 0.81, 0.80, 0.79, 0.78, 0.77, 0.76, 0.75, 0.74, 0.73, 0.72, 0.71, 0.70, 0.69, 0.68, 0.67, 0.66, 0.65, 0.64, 0.63, 0.62, 0.61, 0.60, 0.55, 0.50, 0.45, 0.40, etc.
[0131] Furthermore, the M coating according to the present invention is configured to preferably also provide a very low reflectance in the UV band, and this has very good robustness. This is particularly suitable when the M coating is applied to the front surface of a base element containing a photochromic compound that can be activated in the UV wavelength range.
[0132] Thus, the M coating can have an average reflectance coefficient Ruv in the wavelength range of 280 nm to 380 nm that is less than or equal to 5%, preferably less than or equal to 3.0%, particularly less than or equal to 2.5%, and typically less than or equal to 2.0%.
[0133] As used herein, "an average reflectance coefficient Ruv less than or equal to 5.0%" includes the following values and / or any interval between these values (in %): 5.0, 4.9, 4.8, 4.7, 4.6, 4.5, 4.4, 4.3, 4.2, 4.1, 4.0, 3.9, 3.8, 3.7, 3.6, 3.5, 3.4, 3.3, 3.2, 3.1, 3.0, 2.9, 2.8, 2.7, 2.6, 2.5, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.4, 0.3, 0.2, 0.1, etc.
[0134] In addition, the M coating has an average reflectance coefficient Ruv for an incident angle of 35°, and the standard deviation of the average reflectance coefficient, defined as "σRuv", is less than or equal to 0.50%, preferably less than or equal to 0.45%, and particularly less than or equal to 0.40%.
[0135] Moreover, as used herein, "the standard deviation defined as 'σRuv' is less than or equal to 0.50%" includes the following values and / or any interval (in %) between these values: 0.50, 0.45, 0.40, 0.35, 0.30, 0.25, 0.20, 0.15, 0.10, 0.05, etc.
[0136] In addition, the optical article of the present invention can generally have an ESPF coefficient greater than 20, particularly greater than or equal to 25 and typically greater than or equal to 30, such as 35. From the perspective of UV protection, it is preferred that the glass has an ESPF greater than 25 and preferably greater than 30.
[0137] Different structures of the IF coating according to the present invention deposited on the front main surface and / or the rear main surface of the base element will be described below.
[0138] As previously mentioned, the IF coating presents a specific stack of the following:
[0139] - at least one LI layer,
[0140] - at least one HI layer, and
[0141] - the outermost LI layer, which exhibits a refractive index gradient that gradually decreases in the direction away from the base element and has a maximum refractive index less than 1.55.
[0142] Generally, the outermost layer has a physical thickness less than or equal to 150 nm, preferably equal to or less than 140 nm, and typically equal to or less than 135 nm.
[0143] According to a feature of the present invention, for embodiments in which the IF coating is an AR coating, the outermost layer has a physical thickness less than or equal to 100 nm, preferably equal to or less than 90 nm, and typically equal to or less than 85 nm.
[0144] According to another feature of the present invention, for embodiments in which the IF coating is an M coating, the outermost layer has a physical thickness less than or equal to 150 nm, preferably equal to or less than 145 nm, and typically equal to or less than 140 nm.
[0145] As used herein, "physical thickness less than or equal to 150 nm" includes the following values and / or any interval (in nm) between these values: 150, 145, 140, 135, 130, 125, 120, 115, 110, 105, 100, 99, 98, 97, 95, 95, 94, 93, 92, 91, 90, 89, 88, 87, 86, 85, 84, 83, 82, 81, 80, 79, 78, 77, 76, 75, 74, 73, 72, 71, 70, 69, 68, 67, 66, 65, 64, 63, 62, 61, 60, 55, 50, etc.
[0146] According to one embodiment, the outermost layer of the IF coating can consist of a single layer. Thus, from the inner surface of this single layer facing the base element to the outer surface of this single layer facing the air, the refractive index gradient continuously decreases. In this embodiment, the inner surface of this single layer exhibits the maximum refractive index.
[0147] For this embodiment, generally, the single outermost LI layer of the IF coating can be deposited by evaporating at least one precursor compound using electron beam evaporation in a vacuum chamber with oxygen introduced. Generally, the at least one precursor is SiO2 or a mixture of SiO2 + Al2O3 (silica doped with alumina) and is typically SiO2.
[0148] To obtain a continuously decreasing refractive index gradient in the thickness direction from the inner surface to the outer surface, during the manufacture of the optical article in the vacuum chamber, the oxygen flow rate is continuously increased. For example, the oxygen flow rate can be continuously increased from a lower value to a higher value, such as from 0 sccm to 25 sccm or 50 sccm (or another higher value greater than the lower value). Thus, compared with a standard SiO2 layer in which the refractive index is stable (i.e., does not change) (for which there is no O2 gas flow during its deposition), the refractive index of the single outermost layer continuously decreases in the thickness direction. Additionally, the working pressure during the deposition of the at least one precursor at the above different oxygen flow rates can be respectively: 7.0x 10 -4 Pa (0 sccm O2); 7.0x 10 -3 Pa (25 sccm O2); 1.3x 10 -3 Pa (50 sccm O2); 2.3x 10 -3 Pa (90 sccm O2).
[0149] According to another embodiment, the outermost layer of the IF coating includes:
[0150] - at least two layers, the at least two layers including at least a first layer and a second layer deposited on the first layer, and
[0151] - In particular, at least three layers, said at least three layers including at least a first layer, a second layer deposited on said first layer, and a third layer.
[0152] According to this embodiment, the refractive index gradient decreases layer by layer from the layer closest to the base element / substrate (i.e., the first layer) to the layer closest to air (i.e., the second layer or the third layer or another layer of this outermost sheet layer located farthest from the base element). Thus, herein, the first layer of this single layer exhibits the maximum refractive index.
[0153] Moreover, for this embodiment, the different layers of the outermost LI sheet layer constituting the IF coating can be deposited by evaporating at least one precursor compound using electron beam evaporation in a vacuum chamber with oxygen introduced. Generally, the at least one precursor is SiO2 or a mixture of SiO2 + Al2O3 (silicon dioxide doped with alumina) and typically is SiO2. Additionally, the working pressures during depositing the at least one precursor at the above different oxygen flow rates can be respectively: 7.0x10 -4 Pa (0 sccm O2); 7.0x10 -3 Pa (25 sccm O2); 1.3x10 -3 Pa (50 sccm O2); 2.3x10 -3 Pa (90 sccm O2).
[0154] According to this embodiment,
[0155] - The first layer can correspond to, for example, a standard LI layer made of SiO2 deposited in a vacuum chamber without introducing oxygen (or other gases), or can be deposited by evaporating at least one precursor compound (such as SiO2) using electron beam evaporation in a vacuum chamber with oxygen introduced at a first flow rate;
[0156] - The second layer can be deposited by evaporating at least one precursor compound (such as SiO2) using electron beam evaporation in a vacuum chamber with oxygen introduced at a second flow rate, where the second flow rate is greater than the first flow rate;
[0157] - The optional third layer can be deposited by evaporating at least one precursor compound (such as SiO2) using electron beam evaporation in a vacuum chamber with oxygen introduced at a third flow rate, where the third flow rate is greater than the second flow rate;
[0158] - An optional subsequent layer "n" can be deposited by electron beam evaporation in a vacuum chamber with oxygen introduced at a flow rate of "n", evaporating at least one precursor compound (such as SiO2), where the flow rate of "n" is greater than the flow rate of "n - 1" (the flow rate of "n - 1" corresponds to the flow rate used for depositing the layer below the "n" layer).
[0159] For example, when the outermost laminate of the IF coating comprises two layers, the first flow rate of oxygen can be selected from: 0 sccm, 25 sccm or 50 sccm, and is preferably selected from: 0 sccm or 25 sccm; the second flow rate of oxygen (which is greater than the first flow rate) can be selected from: 25 sccm, 50 sccm or 75 sccm, and is preferably selected from: 50 sccm or 75 sccm.
[0160] Moreover, when the outermost laminate of the IF coating comprises three layers, the first flow rate of oxygen can be selected from: 0 sccm or 25 sccm, and is preferably selected from: 0 sccm; the second flow rate of oxygen (which is greater than the first flow rate) can be selected from: 25 sccm or 50 sccm, and is preferably selected from: 25 sccm, and the third flow rate of oxygen (which is greater than the second flow rate) can be selected from: 50 sccm or 75 sccm, and is preferably selected from: 50 sccm.
[0161] In particular, according to this embodiment, the outermost laminate of the IF coating can comprise two layers:
[0162] - The thickness of the first layer is less than or equal to 55 nm, preferably less than or equal to 50 nm, typically less than or equal to 45 nm and especially in the range of 20 nm to 45 nm, and
[0163] - The thickness of the second layer is less than or equal to 55 nm, preferably less than or equal to 50 nm, typically less than or equal to 45 nm and especially in the range of 20 nm to 45 nm.
[0164] In particular, according to this embodiment, the outermost laminate of the IF coating can comprise three layers:
[0165] - The thickness of the first layer is less than or equal to 50 nm, preferably less than or equal to 45 nm, typically less than or equal to 40 nm and especially in the range of 10 nm to 40 nm,
[0166] - The thickness of the second layer is less than or equal to 50 nm, preferably less than or equal to 45 nm, typically less than or equal to 35 nm and especially in the range of 8 nm to 40 nm, and
[0167] - The thickness of the third layer is less than or equal to 55 nm, preferably less than or equal to 50 nm, typically less than or equal to 45 nm and especially in the range from 10 nm to 50 nm.
[0168] In particular, for embodiments where the IF coating is an M coating, the outermost lamella can comprise three layers:
[0169] - The thickness of the first layer is less than or equal to 50 nm, preferably less than or equal to 48 nm, typically less than or equal to 45 nm and especially in the range from 15 nm to 45 nm,
[0170] - The thickness of the second layer is less than or equal to 50 nm, preferably less than or equal to 48 nm, typically less than or equal to 45 nm and especially in the range from 15 nm to 45 nm, and
[0171] - The thickness of the third layer is less than or equal to 55 nm, preferably less than or equal to 50 nm, typically less than or equal to 45 nm and especially in the range from 20 nm to 50 nm.
[0172] Moreover, according to the present invention, "the thickness of the first layer is less than or equal to 55 nm" includes the following values and / or any interval between these values (in nm): 55, 54, 53, 52, 51, 50, 49, 48, 47, 46, 45, 44, 43, 42, 41, 40, 39, 38, 37, 36, 35, 34, 33, 32, 31, 30, 29, 28, 27, 26, 25, 24, 23, 22, 21, 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, etc.
[0173] In addition, according to the present invention, "the thickness of the first layer is less than or equal to 50 nm" includes the following values and / or any interval between these values (in nm): 50, 49, 48, 47, 46, 45, 44, 43, 42, 41, 40, 39, 38, 37, 36, 35, 34, 33, 32, 31, 30, 29, 28, 27, 26, 25, 24, 23, 22, 21, 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, etc.
[0174] In addition, according to the present invention, "the thickness of the first layer is less than or equal to 45 nm" includes the following values and / or any interval (in nm) included between these values: 45, 44, 43, 42, 41, 40, 39, 38, 37, 36, 35, 34, 33, 32, 31, 30, 29, 28, 27, 26, 25, 24, 23, 22, 21, 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, etc.
[0175] According to the present invention, the IF coating further includes at least one layer having a low refractive index defined as "LI layer" and less than 1.55 and at least one layer having a high refractive index defined as "HI layer" and equal to or greater than 1.55.
[0176] The HI layer and the LI layer do not have to alternate with each other in the stack of the IF coating, although according to an embodiment of the present invention, they may also alternate. Two (or more) HI layers can be deposited on top of each other, and two (or more) LI layers can be deposited on top of each other. Generally, the HI layer and the LI layer alternate with each other in the stack of the IF coating according to the present invention.
[0177] In the present application, when two (or more) HI layers are deposited on top of each other, they are not considered as a single HI layer when counting the number of layers of the interference stack. The same applies to the stack of two or more adjacent LI layers. However, in the following description, when counting the number of layers constituting the IF coating according to the present invention, the outermost LI sheet layer is considered as "one LI layer" (regardless of which embodiment, i.e., a single layer or composed of two or three layers).
[0178] Here is a simple stack because the total number of layers in the IF coating (including the outermost LI sheet layer) is greater than or equal to 3 and generally less than or equal to 16.
[0179] - According to an aspect of the present invention, the total number of HI layers and LI layers in the IF coating is greater than or equal to 3, preferably greater than or equal to 4, more preferably greater than or equal to 5 and typically greater than or equal to 6, such as greater than or equal to 7.
[0180] - According to another aspect of the present invention, the total number of HI layers and LI layers in the IF coating is less than or equal to 16, especially less than or equal to, preferably less than or equal to 15, more preferably less than or equal to 13 and typically less than or equal to 12.
[0181] For example, the total number of HI layers and LI layers (including the outermost LI sheet layer) in the IF coating ranges from 4 to 6 layers, preferably 5 to 6 layers.
[0182] The structures of other LI layers and HI layers will be described below.
[0183] Typically, the HI layer is a conventional high refractive index layer well known in the art. They usually contain one or more metal oxides, such as, by way of non-limiting example, zirconium oxide (ZrO2), titanium oxide (TiO2), titanium sesquioxide (Ti3O5), aluminum oxide (Al2O3), tantalum pentoxide (Ta2O5), neodymium oxide (Nd2O5), praseodymium oxide (Pr2O3), praseodymium titanate (PrTiO3), La2O3, Nb2O5, or Y2O3. Optionally, the high refractive index layer may also contain silica or other low refractive index materials, provided that their refractive index is greater than 1.6 as specified above. Preferred materials are TiO2, PrTiO3, ZrO2, Ta2O5, Al2O3, Y2O3 and mixtures thereof. Preferably, the one or more HI layers are made of zirconium oxide (ZrO2).
[0184] The LI layer is also a well-known low refractive index layer and may comprise, by way of non-limiting example: silica, or alternatively a mixture of silica and alumina, especially silica doped with alumina, which helps to increase the thermal resistance of the UV reflective interference coating. Each LI layer is preferably a layer containing at least 80% by weight, more preferably at least 90% by weight, and even more preferably consisting of a silica layer (i.e., not obtained by electron beam evaporation of at least one precursor compound (such as SiO2) in a vacuum chamber with the introduction of oxygen) relative to the total weight of the layer.
[0185] Optionally, the low refractive index layer may also contain a high refractive index material, provided that the refractive index of the resulting layer is less than 1.55.
[0186] When using an LI layer comprising a mixture of SiO2 and Al2O3, it preferably contains 1% to 10% by weight, more preferably 1% to 8% by weight, and even more preferably 1% to 5% by weight of Al2O3 relative to the total weight of SiO2+Al2O3 in this layer. For example, SiO2 doped with 4% or less by weight of Al2O3, or SiO2 doped with 8% Al2O3 can be used. Commercially available SiO2 / Al2O3 mixtures can be used, such as the mixture (refractive index at 550 nm included between n = 1.48 - 1.50 nm) sold by Umicore Materials AG or the substance (refractive index n = 1.48 at 500 nm) sold by Merck KGaA.
[0187] The optical article of the present invention (such as an ophthalmic lens) can be made antistatic by bonding at least one conductive layer to a laminate present on the surface of the ophthalmic lens, i.e., it does not retain and / or does not form a large amount of static charge.
[0188] This conductive layer is preferably located between two layers of the IF coating and / or adjacent to the high refractive index layer of this IF coating. Preferably, the conductive layer is directly under the outermost LI laminate of the IF coating and ideally forms the penultimate layer of the IF coating, i.e., it is directly under the outermost LI laminate of the IF coating according to the present invention.
[0189] The conductive layer must be thin enough not to reduce the transparency of the UV reflective interference coating. The conductive layer is preferably made of a conductive and highly transparent material (usually an optionally doped metal oxide). In this case, the thickness of the conductive layer preferably ranges from 1 nm to 15 nm and more preferably from 1 nm to 10 nm. The conductive layer preferably contains an optionally doped metal oxide selected from indium oxide, tin oxide (SnO2), zinc oxide, and mixtures thereof. Preferably indium tin oxide (tin-doped indium oxide, In2O3:Sn), aluminum-doped zinc oxide (ZnO:Al), indium oxide (In2O3), and tin oxide (SnO2). According to an optimum embodiment, the conductive and optically transparent layer is an indium tin oxide (ITO) layer or a tin oxide (SnO2) layer.
[0190] Generally, the conductive layer within the laminate but to a limited extent due to its small thickness contributes to obtaining antireflection properties and forms a high refractive index layer (also considered an HI layer when counting the number of layers) in the AR coating. This is the case for a layer made of a conductive and highly transparent material such as an ITO layer.
[0191] According to another aspect of the present invention, the IF coating (including the outermost LI laminate) has a total physical thickness of less than or equal to 1 μm, particularly less than or equal to 900 nm, and typically less than or equal to 750 nm.
[0192] As used herein, "a thickness of less than or equal to 1 μm" includes the following values (in nm) and / or any interval between these values (including the limiting values): 1000, 950, 900, 850, 800, 790, 780, 770, 760, 750, 740, 730, 720, 710, 700, 690, 680, 670, 660, 650, 640, 630, 620, 610, 600, 590, 580, 570, 560, 550, 540, 530, 520, 510, 500, 490, 480, 470, 460, 450, 440, 430, 420, 410, 400, 380, 350, 320, 300, 280, 250, 240, 220, 200, 180, etc.
[0193] In particular, each HI layer of the IF coating has a physical thickness of less than or equal to 170 nm, such as less than or equal to 120 nm, preferably less than or equal to 110 nm, and more preferably less than or equal to 100 nm.
[0194] According to a feature of the present invention, for embodiments in which the IF coating is an AR coating, each HI layer of the AR coating can have a physical thickness of less than or equal to 120 nm, preferably less than or equal to 110 nm, and more preferably less than or equal to 100 nm.
[0195] According to another feature of the present invention, for embodiments in which the IF coating is an M coating, each HI layer of the M coating can have a physical thickness of less than or equal to 120 nm, preferably less than or equal to 110 nm, and more preferably less than or equal to 100 nm, except that the outermost HI layer can have a physical thickness of greater than or equal to 80 nm, preferably greater than or equal to 120 nm, such as greater than or equal to 150 nm (and less than or equal to 170 nm).
[0196] In addition, except for the LI outermost lamina, each LI layer of the IF coating generally has a physical thickness of less than or equal to 80 nm, preferably less than or equal to 70 nm, more preferably less than or equal to 60 nm, and typically less than or equal to 50 nm.
[0197] As used herein, "a physical thickness of less than or equal to 80 nm" includes the following values (in nm) and / or any interval between these values (including the limiting values): 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, etc.
[0198] Typically, the outermost LI laminate of the IF coating has a physical thickness of less than or equal to 250 nm, such as less than or equal to 150 nm, preferably less than or equal to 140 nm, more preferably less than or equal to 135 nm and typically less than or equal to 130 nm. In particular, the outermost LI laminate has a physical thickness of greater than or equal to 50 nm, preferably greater than or equal to 55 nm and typically greater than or equal to 60 nm. In particular, for embodiments in which the IF coating is an M coating, the outermost LI laminate has a physical thickness of less than or equal to 250 nm, such as less than or equal to 240 nm, preferably less than or equal to 230 nm, more preferably less than or equal to 220 nm.
[0199] As used herein, "physical thickness of less than or equal to 250 nm" includes the following values (in nm) and / or includes any interval between these values (including the limiting values): 250, 240, 230, 220, 210, 200, 190, 180, 170, 160, 150, 80, 75, 70, 65, 60, 55, 50.
[0200] In addition, the innermost layer of the IF coating (that is, the layer closest to the base element / substrate among all the layers of the IF coating) is the HI layer. This innermost HI layer has a physical thickness of less than or equal to 110 nm, such as less than or equal to 50 nm, preferably less than or equal to 45 nm, more preferably less than or equal to 40 nm and typically less than or equal to 35 nm. In particular, for embodiments in which the IF coating is an M coating, the innermost HI layer has a physical thickness of less than or equal to 110 nm, preferably less than or equal to 105 nm, more preferably less than or equal to 100 nm, and the physical thickness can typically be less than or equal to 50 nm.
[0201] For example, according to one embodiment, the IF coating (such as an AR coating) includes, in order starting from the base element / substrate optionally coated with one or more functional coatings:
[0202] (1) The innermost HI layer, which has a physical thickness of less than or equal to 50 nm, in particular in the range of 5 nm to 50 nm, preferably in the range of 8 nm to 45 nm, and typically in the range of 8 nm to 40 nm, such as 10 nm to 35 nm;
[0203] (2) The LI layer, which has a physical thickness of less than or equal to 80 nm, in particular in the range of 5 nm to 70 nm, preferably in the range of 8 nm to 60 nm, and typically in the range of 8 nm to 50 nm, such as in the range of 8 nm to 40 nm, such as 8 nm to 35 nm;
[0204] (3) The HI layer, having a physical thickness less than or equal to 130 nm, particularly in the range of 55 nm to 130 nm, preferably in the range of 60 nm to 125 nm, and typically in the range of 65 nm to 110 nm;
[0205] (4) An optional antistatic layer, having a physical thickness less than or equal to 15 nm, particularly in the range of 4 nm to 10 nm;
[0206] (5) The outermost LI sheet layer, having a physical thickness less than or equal to 150 nm, particularly in the range of 55 nm to 130 nm, preferably in the range of 60 nm to 100 nm, and typically in the range of 65 nm to 90 nm.
[0207] According to another embodiment, the IF coating (such as an AR coating) comprises, in order starting from a base element / substrate optionally coated with one or more functional coatings:
[0208] (1) The innermost HI layer, having a physical thickness less than or equal to 50 nm, particularly in the range of 5 nm to 50 nm, preferably in the range of 8 nm to 45 nm, and typically in the range of 10 nm to 40 nm, such as 8 nm to 35 nm;
[0209] (2) The LI layer, having a physical thickness less than or equal to 80 nm, particularly in the range of 5 nm to 70 nm, preferably in the range of 8 nm to 60 nm, and typically in the range of 8 nm to 50 nm, such as in the range of 8 nm to 40 nm, such as 8 nm to 35 nm;
[0210] (3) The HI layer, having a physical thickness less than or equal to 130 nm, particularly in the range of 55 nm to 130 nm, preferably in the range of 60 nm to 125 nm, and typically in the range of 65 nm to 110 nm;
[0211] (4) The LI layer, having a physical thickness less than or equal to 50 nm, particularly in the range of 5 nm to 50 nm, preferably in the range of 8 nm to 40 nm, and typically in the range of 8 nm to 30 nm, such as in the range of 8 nm to 20 nm, such as 8 nm to 15 nm;
[0212] (5) An optional antistatic layer, having a physical thickness less than or equal to 15 nm, particularly in the range of 4 nm to 10 nm;
[0213] (6) The outermost LI sheet layer, having a physical thickness less than or equal to 150 nm, particularly in the range of 55 nm to 130 nm, preferably in the range of 60 nm to 100 nm, and typically in the range of 65 nm to 90 nm.
[0214] For example, according to one embodiment, the IF coating (such as the M coating) comprises, in the order starting from a base element / substrate optionally coated with one or more functional coatings:
[0215] (1) The innermost HI layer having a physical thickness less than or equal to 110 nm, particularly in the range of 5 nm to 110 nm, preferably in the range of 10 nm to 105 nm, and typically in the range of 15 nm to 105 nm, such as 25 nm to 100 nm;
[0216] (2) The LI layer having a physical thickness less than or equal to 80 nm, particularly in the range of 3 nm to 70 nm, preferably in the range of 3 nm to 60 nm, and typically in the range of 3 nm to 50 nm, such as in the range of 8 nm to 40 nm, such as 8 nm to 35 nm;
[0217] (3) The HI layer having a physical thickness less than or equal to 130 nm, particularly in the range of 10 nm to 130 nm, preferably in the range of 10 nm to 125 nm, and typically in the range of 20 nm to 80 nm;
[0218] (4) The LI layer having a physical thickness less than or equal to 250 nm, particularly in the range of 80 nm to 240 nm, preferably in the range of 85 nm to 230 nm, and typically in the range of 90 nm to 220 nm;
[0219] (5) The HI layer having a physical thickness less than or equal to 160 nm, particularly in the range of 50 nm to 160 nm, preferably in the range of 60 nm to 160 nm, and typically in the range of 70 nm to 160 nm;
[0220] (6) The outermost LI lamina having a physical thickness less than or equal to 150 nm, particularly in the range of 60 nm to 145 nm, preferably in the range of 80 nm to 145 nm, and typically in the range of 90 nm to 140 nm.
[0221] B.3 Sub-layer
[0222] In one embodiment of the present invention, the IF coating can be (usually directly) deposited onto a sub-layer (i.e., the sub-layer is located between the substrate and the interference coating), also referred to as the "underlayer". It should be noted that such a sub-layer does not belong to the IF coating according to the present invention. The expression "sub-layer" should be understood to mean a coating having a relatively large thickness, which is used for the purpose of improving mechanical properties, such as the wear and / or scratch tolerance of the coating and / or promoting its adhesion to the substrate or to the underlying coating.
[0223] Due to its relatively large thickness, the underlayer generally does not participate in the interference optical activity, especially when it has a refractive index similar to that of the underlying coating (which is usually a wear-resistant and scratch-resistant coating) or the substrate when the underlayer is directly deposited on the substrate. Therefore, the underlayer (when present) is not considered to form part of the reflection characteristics of the IF coating.
[0224] The underlayer must be thick enough to increase the wear tolerance of the IF coating, but preferably not too thick so as not to absorb light, as depending on the nature of the underlayer, this can significantly reduce the relative transmittance τ. v . The thickness of the underlayer is generally less than 300 nm and even better less than 200 nm and generally greater than 90 nm and even better greater than 100 nm.
[0225] The underlayer preferably comprises a SiO2-based layer which preferably comprises at least 80% by weight, and even better at least 90% by weight, of silica relative to the total weight of the layer, and even better still this layer consists of a silica layer. The thickness of this SiO2-based layer is generally less than 300 nm and even better less than 200 nm, and generally greater than 90 nm and even better less than 100 nm. According to another embodiment, this SiO2-based layer is a layer of silica doped with alumina in the proportions defined above and preferably consists of a layer of silica doped with alumina.
[0226] According to a specific embodiment, the underlayer consists of a SiO2 layer. Preferably, the underlayer is a single layer.
[0227] However, the underlayer can be laminated (i.e.: multiple sub-layers), especially when there is a non-negligible refractive index difference between the underlayer and the underlying coating (or the substrate if the underlayer is directly deposited on the substrate). In addition to the main layer (described above), such multiple sub-layers generally include a layer having a high refractive index and having a thickness of less than or equal to 80 nm, more preferably less than or equal to 50 nm and most preferably less than or equal to 30 nm. This layer having a high refractive index is in direct contact with a substrate having a high refractive index or the underlying coating having a high refractive index (when appropriate). Of course, this embodiment can also be used even if the substrate (or the underlying coating) has a refractive index of less than 1.55.
[0228] As an alternative, in addition to the main layer and the aforementioned layer with a high refractive index, the sub-layer further includes a layer made of a SiO2-based material (i.e., preferably containing at least 80% by weight of silicon dioxide), the layer having a refractive index less than or equal to 1.55, preferably less than or equal to 1.52, more preferably less than or equal to 1.50, and having a thickness less than or equal to 80 nm, more preferably less than or equal to 50 nm and even more preferably less than or equal to 30 nm, on which the layer with a high refractive index is deposited. Typically, in this case, the sub-layer includes (deposited in this order onto an optionally coated substrate) a SiO2 layer 10 - 25 nm thick (such as a SiO2 layer 15 - 20 nm thick), a ZrO2 or Ta2O5 layer 5 - 15 nm thick (such as a ZrO2 or Ta2O5 layer 5 - 10 nm thick), and then the main layer of the sub-layer.
[0229] B.4 Other functional layers
[0230] In some applications, it is preferred that the main surface of the substrate is coated with one or more functional coatings before depositing the interference coating of the present invention to improve its optical properties and / or mechanical properties.
[0231] These functional coatings conventionally used for optical devices can be but are not limited to an impact-resistant primer layer, an internal anti-abrasion coating (also known as a hard coating), an antistatic coating especially on the concave surface of an optical article, or a laminate made of two or more of such coatings. Preferably, an ophthalmic lens does not include a photochromic coating and / or does not include a photochromic substrate.
[0232] Figure 1 An optical article according to an embodiment of the present invention is shown.
[0233] Generally and by reference Figure 1 , an optical article according to the present invention (such as ophthalmic lens 300) includes a base element / substrate 301, and the base element / substrate is successively coated on its front 303 with an impact-resistant primer layer 304, an anti-abrasion and / or scratch-resistant layer 305, an IF coating 306 according to the present invention, and optionally a hydrophobic and / or oleophobic coating (not shown). The optical article according to the present invention is preferably an ophthalmic lens (spectacle lens) for a pair of glasses, or an ophthalmic lens blank. The lens can be a polarized lens, a photochromic lens, or a tinted sunglass lens, optionally providing correction.
[0234] In addition, the back 302 of the optical article (such as an ophthalmic lens substrate) can be successively coated with an impact-resistant primer layer 304, an anti-abrasion and / or scratch-resistant layer 307, an IF coating 306 according to the present invention, and optionally a hydrophobic and / or oleophobic coating (not shown).
[0235] In one embodiment, the optical article according to the invention does not absorb or does not absorb much in the visible light, which means that, in the context of the present application, its transmission coefficient τ V (also known as the relative transmission coefficient in the visible light range) is greater than 90%, more preferably greater than 95%, even more preferably greater than 96% and most preferably greater than 97%.
[0236] Coefficient τ V should be understood as defined by the international standard definition (ISO 13666:1998 standard) and measured according to the ISO8980-3 standard. It is defined in the wavelength range of 380 nm to 780 nm.
[0237] Preferably, the light absorption rate of the article coated according to the invention is less than or equal to 1%.
[0238] B.41 Wear-resistant and / or scratch-resistant coatings
[0239] The wear-resistant and / or scratch-resistant coatings are preferably poly(meth)acrylate-based or silane-based hard coatings, which usually contain one or more mineral fillers, and these mineral fillers are intended to increase the hardness and / or refractive index of the coating after curing.
[0240] The hard wear-resistant and / or scratch-resistant coatings are preferably prepared from a composition containing at least one alkoxysilane and / or its hydrolysis product, and the hydrolysis product is obtained, for example, by hydrolysis with a hydrochloric acid solution and optionally a condensation and / or curing catalyst.
[0241] Among the coatings recommended in the present invention, mention may be made of coatings based on the hydrolysis products of epoxy silanes, such as those described in patents FR 2702486 (EP 0614957), US 4211823 and US 5015523.
[0242] The preferred composition for the wear-resistant and / or scratch-resistant coatings is the composition disclosed in the name of the applicant in patent FR 2702486. The composition contains the hydrolysis products of epoxy trialkoxysilane and dialkyldialkoxysilane, colloidal silica, and a catalytic amount of an aluminum-based curing catalyst such as aluminum acetylacetonate, and the remainder consists essentially of solvents conventionally used for formulating such compositions. Preferably, the hydrolysis products used are the hydrolysis products of γ-glycidoxypropyltrimethoxysilane (GLYMO) and dimethyldiethoxysilane (DMDES).
[0243] The wear-resistant and / or scratch-resistant coating composition can be deposited on the main surface of the substrate by dip coating or spin coating. Subsequently, it is cured by an appropriate means (preferably heat or UV).
[0244] The thickness of the wear-resistant and / or scratch-resistant coating typically varies from 2 μm to 10 μm, preferably from 3 μm to 5 μm.
[0245] B.42 Primer coating
[0246] Prior to depositing the wear-resistant and / or scratch-resistant coating, it is possible to deposit a primer coating on the substrate, which improves the impact resistance and / or adhesion of the subsequent layers in the final product. This coating can be any impact-resistant primer layer conventionally used for articles made of transparent polymeric materials, such as ophthalmic lenses.
[0247] Among the preferred primer compositions, mention may be made of compositions based on thermoplastic polyurethane, such as those described in patents JP 63-141001 and JP 63-87223; poly(meth)acrylate primer compositions, such as those described in patent US 5 015 523; compositions based on thermosetting polyurethane, such as those described in patent EP 0 404 111; and compositions based on poly(meth)acrylate latex or polyurethane-based latex, such as those described in patents US 5 316 791 and EP 0 680 492.
[0248] Preferred primer compositions are polyurethane-based compositions and latex-based compositions, especially polyurethane latex optionally containing polyester units.
[0249] Among the commercially available primer compositions suitable for the present invention, mention may be made of the following: Witcobond(R) 232, Witcobond(R) 234, Witcobond(R) 240, Witcobond(R) 242, Neorez(R) R-962, Neorez(R) R-972, Neorez(R) R-986, and Neorez(R) R-9603.
[0250] Blends of primer compositions of these latexes can also be used, especially blends of primer compositions of polyurethane latex and poly(meth)acrylate latex.
[0251] These primer compositions can be deposited on the surface of the article by dip coating or spin coating and then dried at a temperature of at least 70 °C and possibly up to 100 °C and preferably about 90 °C for 2 minutes to 2 hours and typically about 15 minutes in order to form a primer layer having a thickness of 0.2 to 2.5 μm and preferably 0.5 to 1.5 μm after baking.
[0252] B.43 Hydrophobic coating and / or oleophobic coating
[0253] The ophthalmic lens according to the present invention may further comprise a coating formed on the UV-reflective interference coating and capable of changing its surface properties, such as a hydrophobic coating and / or an oleophobic coating (anti-fouling top coating). These coatings are preferably deposited on the outer layer of the UV-reflective interference coating. They are generally less than or equal to 10 nm thick, preferably 1 to 10 nm thick and more preferably 1 to 5 nm thick.
[0254] This is generally a problem of fluorosilane or fluorosilazane coatings. These coatings can be obtained by depositing a fluorosilane or fluorosilazane precursor preferably containing at least two hydrolyzable groups per molecule. The fluorosilane precursor preferably contains a fluoropolyether group and more preferably a perfluoropolyether group. These fluorosilanes are well-known and are particularly described in patents US 5,081,192, US 5,763,061, US 6,183,872, US 5,739,639, US 5,922,787, US 6,337,235, US 6,277,485 and EP0933377.
[0255] A preferred hydrophobic and / or oleophobic coating composition is sold by Shin-Etsu Chemical under the name KP 801M(R). Another preferred hydrophobic and / or oleophobic coating composition is sold by Daikin Industries under the name OPTOOL DSX(R). This is a problem of a fluororesin containing perfluoropropene groups.
[0256] C) Method
[0257] The present invention also relates to a method for manufacturing an optical article as defined in any one of the preceding claims, which comprises the following steps:
[0258] (a) providing a base element having a front main surface and a rear main surface;
[0259] (b) depositing in a vacuum chamber onto the front main surface and / or the rear main surface, the interference multilayer coating comprising the outermost sheet layer,
[0260] wherein the outermost sheet layer is deposited by electron beam evaporation of at least one precursor compound in a vacuum chamber with oxygen being introduced, and the flow rate of oxygen is gradually increased during the deposition of the outermost sheet layer.
[0261] In particular, the at least one precursor compound is silicon oxide or a mixture of SiO2+Al2O3 (silicon dioxide doped with alumina) and typically is SiO2.
[0262] In particular, the outermost layer is obtained according to the method as described above in paragraph (B.2), and will not be repeated hereinafter.
[0263] The other layers of the IF coating and the above-mentioned sub-layers are preferably deposited by vapor deposition in a vacuum deposition chamber under vacuum according to any one of the following methods:
[0264] i) Evaporation, optionally assisted by an ion beam;
[0265] ii) Ion beam spraying;
[0266] iii) Cathode sputtering;
[0267] iv) Plasma-assisted chemical vapor deposition.
[0268] These different methods are described respectively in the following reference documents "Thin Film Processes" and "Thin Film Processes II", edited by Vossen & Kern, Academic Press, 1978 and 1991. The particularly recommended method is evaporation under vacuum. Preferably, the deposition of each of the above layers is carried out by evaporation under vacuum. This method indeed advantageously avoids heating the substrate, which is particularly meaningful for coating heat-sensitive substrates (such as plexiglass).
[0269] Naturally, the various embodiments described above for optical articles are also applicable to this method of manufacturing optical articles, and will not be repeated hereinafter.
[0270] Examples
[0271] A) Characterization
[0272] Optical measurements and colorimetric measurements (reflection) were performed on the surface of the base element (i.e., the substrate) coated with an exemplary interference multilayer coating (front) on its front surface and / or back surface using a spectrophotometer: average reflection coefficients Rv, Ruv, hue angle h, chromaticity C* in the international colorimetric CIE (L*, a*, b*) space, taking into account the standard light source D65 and the standard observer 10° (for h and C*). For forward reflection (Cx plane), they are provided for an incident angle of 15°, and for backward reflection (Cc plane), they are provided for an incident angle of 35°.
[0273] B) General procedure
[0274] The ophthalmic lenses used in the examples include lens substrates (D1 to D9) or Lens substrates (D10), these substrates having a diameter of 65 mm, a refractive index of 1.60, a diopter of -2.00 and a thickness of 1.2 mm, coated on their front and back with product Elis corresponding to 3.5 μm thick A hard and scratch-resistant coating (hard coating) (refractive index 1.6) of Essilor, followed by an anti-reflection multi-layer interference coating according to the invention.
[0275] The layers of the anti-reflection coating are deposited by vacuum evaporation (evaporation source: electron gun) (without introducing an oxygen stream) without heating the substrate.
[0276] The deposition tool is a Satis 1200DLF machine equipped with a Temescal (8 kV) electron gun for evaporating oxides and an (IPC) (Veeco Mark II) ion gun for the preparatory stage of preparing the substrate surface with argon ions.
[0277] The thickness of the layers is controlled by a quartz microbalance. Spectral measurements are carried out using a variable angle Perkin-Elmer lambda 850 spectrophotometer with a universal reflection attachment (URA).
[0278] The outermost layer of the exemplary interference coating according to the invention is deposited by electron beam evaporation of SiO2 as a precursor with oxygen introduced at different flow rates, the flow rates being gradually increased according to the example: 0 sccm, 25 sccm, 50 sccm. Hereinafter, the layer obtained with 25 sccm of O2 introduced will be referred to as "pQ25", and the layer obtained with 50 sccm of O2 introduced will be referred to as "pQ50". In these examples according to the invention, this outermost layer comprises two or three layers with a decreasing refractive index gradient in the direction away from the substrate. Comparative lenses are also manufactured, where the outermost layer is a single layer made of SiO2 obtained by vacuum evaporation (i.e., 0 sccm of O2) or where the outermost layer is deposited by electron beam evaporation of SiO2 as a precursor with oxygen introduced at a constant flow rate of 50 sccm ("pQ50").
[0279] C) Test procedure
[0280] A method for preparing an ophthalmic lens includes introducing a substrate coated on its front face with a wear-resistant and scratch-resistant coating into a vacuum deposition chamber, a step of evacuating the chamber until a secondary vacuum is obtained, a step of activating the surface of the substrate with an argon ion beam (anode current: 1 A, anode voltage: 100 V, neutralization current: 130 mA), turning off the ion irradiation, optionally forming an underlayer (hereinafter "UL") on the substrate by evaporation, then subsequently forming the respective layers of an antireflection coating by successive evaporation (such as those shown in the following different tables), and a final venting step.
[0281] D) Tested lenses and results
[0282] D.1 Lenses 1 to 4 according to the invention and comparative lenses 1 to 4 (antireflection characteristics)
[0283] Table 1 below shows the structural and optical characteristics of reference lens Comparative Example 1 compared with lenses 1 to 4 according to the invention. Lenses 1 to 4 have been obtained by replacing the standard SiO2 outermost layer (with a stable refractive index) with the outermost LI sheet layer according to the invention comprising two or three layers and having a decreasing refractive index gradient in the direction away from the substrate.
[0284]
[0285] Table 1 above shows the layer structure of the standard antireflection coating (i.e.: Comparative Example 1). By replacing the outermost SiO2 layer with the outermost sheet layer according to the invention comprising three layers: SiO2 + pQ25 + pQ50 in the thickness direction away from the substrate, the new AR coating according to the invention (i.e.: lens 1) has been obtained from the reference antireflection coating Comparative Example 1. As described above, in the examples, pQ25 and pQ50 are SiO2 layers deposited at oxygen flow rates of 25 sccm and 50 sccm respectively. Thus, in lens 1 according to the invention, the outermost sheet layer composed of SiO2 + pQ25 + pQ50 has a decreasing refractive index gradient.
[0286] Table 1 also compares the reflection characteristics of at least the AR coating of Comparative Example 1 and Lens 1. The Rv and σRv of Comparative Example 1 are slightly greater than those values of Lens 1. Most importantly, interestingly, it is noted that the color robustness of Lens 1 is significantly better (with lower σh* and σC* values) than that of Comparative Example 1, which is actually beneficial for mass production. As shown by the examples of Lenses 2 to 4 in Table 1, the outermost LI layer can consist of two layers: (Lens 2) SiO2 + pQ25, or (Lens 3) SiO2 + pQ50, or (Lens 4) pQ25 + pQ50. Table 1 also compares the reflection characteristics of four Lenses 1 to 4 according to the present invention and designed from the reference AR coating Comparative Example 1. Interestingly, it is noted that among all these Lenses 1 to 4, Lens 1 with the outermost layer consisting of three layers (SiO2 + pQ25 + pQ50) exhibits the best colorimetric robustness (with the lowest σh* and σC* values) and σRv. However, Lenses 2 to 4 show better optical and color robustness than the reference lens Comparative Example 1.
[0287] D.2 Lens 5 according to the present invention and Comparative Lens 2 (antireflection characteristics)
[0288] The following Table 2 shows the structural and optical characteristics of the reference lens Comparative Example 2 compared to Lens 5 according to the present invention. Lens 5 has been obtained by replacing the standard SiO2 outermost layer (with a stable refractive index) with the outermost LI layer according to the present invention which includes three layers here: SiO2 + pQ25 + pQ50 and has a reduced refractive index gradient in the direction away from the substrate.
[0289]
[0290]
[0291] Table 2
[0292] Table 2 shows that both the Rv (and also σRv) and Ruv of Lens 5 are less than those of the standard Comparative Example 2. In addition, the colorimetric robustness of Lens 5 according to the present invention is significantly better (with lower σh* and σC* values) than that of the standard Comparative Example 2, which is beneficial for mass production. It is also noted that the σRuv of Lens 5 is significantly less than that of the standard Comparative Example 2. The calculated ESPF value of Comparative Example 2 is 33, which may indicate some practical difficulties in achieving the target ESPF value of 35. However, on the other hand, the calculated ESPF value of the new Lens 5 is 35, which makes it more reliable to achieve the target ESPF value.
[0293] D.3 Lens 6 according to the present invention (antireflection characteristics)
[0294] Table 3 below shows the structure and optical characteristics of the lens 6 according to the present invention. The lens 6 has been obtained by replacing the standard SiO2 outermost layer (with a stable refractive index) with the outermost LI sheet layer according to the present invention, which includes three layers here: SiO2 + pQ25 + pQ50 and has a decreasing refractive index gradient in the direction away from the substrate.
[0295]
[0296] Table 3
[0297] Table 3 shows that the new IF coating (lens 6) according to the present invention exhibits excellent AR performance, including lower Rv and σRv, better robustness (low σh* and σC* values). This lens 6 with a gradient-decreasing refractive index outermost layer is actually desirable for mass production due to its good reproducibility and easier setup.
[0298] D.4 Lenses 7 and Comparative Lens 3 (antireflection characteristics) according to the present invention
[0299] Table 4 below shows the structure and optical characteristics of the reference lens Comparative Example 3 compared with the lens 7 according to the present invention. The lens 7 has been obtained by replacing the standard SiO2 outermost layer (with a stable refractive index) with the outermost LI sheet layer according to the present invention, which includes three layers here: SiO2 + pQ25 + pQ50 and has a decreasing refractive index gradient in the direction away from the substrate.
[0300]
[0301] Table 4
[0302] Table 4 shows that the new IF coating (lens 7) according to the present invention exhibits better AR performance than the reference coating (Comparative Example 3) with a uniform outermost SiO2 layer, including lower Rv and σRv, better robustness (lower σh* and σC* values), and / or lower Ruv and lower σRuv. This lens 7 with a gradient-decreasing refractive index outermost layer is actually desirable for mass production due to its good reproducibility and easier setup. The new lens 7 with the outermost sheet layer according to the present invention shows much better dispersion. It can effectively reduce σh* from 11.7 to 6.9 and σC* from 1.9 to 1.4. Therefore, this new lens 7 is easier to setup.
[0303] D.5 Lens 8 (antireflection characteristics) according to the present invention
[0304] Table 5 below shows the structure and optical characteristics of the lens 8 according to the present invention. The lens 8 has been obtained by replacing the standard SiO2 outermost layer (with a stable refractive index) with the outermost LI film layer according to the present invention, which includes three layers here: SiO2 + pQ25 + pQ50 and has a decreasing refractive index gradient in the direction away from the substrate.
[0305]
[0306] Table 5
[0307] Table 5 shows that the new AR coating (lens 8) according to the present invention exhibits excellent AR performance, including lower Rv and σRv, better robustness (lower σh* and σC* values), and / or lower Ruv and lower σRuv. This lens 8 with a gradient-decreasing refractive index outermost layer is actually desirable for mass production due to its good reproducibility and easier setup.
[0308] D.6 Lens 9 and Comparative Lens 4 (anti-reflection characteristics) according to the present invention
[0309] Table 6 below shows the structure and optical characteristics of the reference lens Comparative Example 4 compared with the lens 9 according to the present invention. The lens 9 has been obtained by replacing the standard SiO2 outermost layer (with a stable refractive index) with the outermost LI film layer according to the present invention, which includes three layers here: SiO2 + pQ25 + pQ50 and has a decreasing refractive index gradient in the direction away from the substrate.
[0310]
[0311] Table 6
[0312] Table 6 shows that the new AR coating (lens 9) according to the present invention exhibits better AR performance than the reference coating (Comparative Example 4) with a uniform outermost SiO2 layer, including lower Rv and σRv, better robustness (lower σh* and σC* values), and / or lower Ruv and lower σRuv. This lens 9 with a gradient-decreasing refractive index outermost layer is actually desirable for mass production due to its good reproducibility and easier setup. The calculated ESPF value of Comparative Example 4 is slightly lower than 35, which may indicate some practical difficulties in achieving the target ESPF value of 35. However, on the other hand, the calculated ESPF value of the new lens 9 is greater than 38, which makes it more reliable to achieve the target ESPF value of 35.
[0313] D.7 Comparative Examples
[0314] Tables 7 to 9 below respectively show the structures and optical characteristics of comparative lens 5 (Comparative Example 5) and another comparative lens 6 (Comparative Example 6) compared with Comparative Example 1 / lens 1 according to the present invention and Comparative Example 2 / lens 5 according to the present invention. In these Comparative Examples 5 and 6, the outermost LI layer / sheet has been replaced by a layer with a stable refractive index deposited by evaporating SiO2 using electron beam evaporation with a regular flow rate of 50 sccm of oxygen introduced in a vacuum chamber. This layer is called pQ50.
[0315]
[0316] Table 7
[0317] The optical and color characteristics of Comparative Example 7 have been compared with those of reference lens Comparative Example 1 and lens 1 according to the present invention (similar structure) (see Table 8).
[0318] Rv σRv h σh <![CDATA[C * > σC* Comparative example 1 0.65 0.09 135 4.6 9.0 2.1 Lens 1 0.61 0.07 135 2.5 9.0 1.5 Comparative example 5 0.59 0.10 135 3.1 9.0 2.0
[0319] Table 8
[0320] Table 8 compares the reflection characteristics of the AR coating of Comparative Example 5 (the outermost LI layer consists of pQ50) with those of Comparative Example 1 (reference lens) and lens 1 (lens according to the present invention including the outermost LI sheet layer having a reduced refractive index gradient in its thickness direction). It is found that Comparative Example 5 has a lower Rv than both lens 1 and Comparative Example 1. Its σRv and colorimetric robustness (σh and σC* values) are very close to those of Comparative Example 1, but are worse than those of lens 1.
[0321] In addition, the optical and color characteristics of Comparative Example 6 have been compared with those of reference lens Comparative Example 2 and lens 5 according to the present invention (similar structure) (see Table 9):
[0322] Rv σRv Ruv σRuv ESPF h σh C* σC* Comparative example 2 0.71 0.10 2.04 0.33 33.09 135 7.6 9 2.0 Lens 5 0.67 0.08 1.84 0.22 39.80 135 5.9 9 1.7 Comparative example 6 0.64 0.11 1.82 0.38 33.90 135 6.6 9 2.1
[0323] Table 9
[0324] Table 9 compares the reflection characteristics of Comparative Example 6 including the outermost LI layer consisting of pQ50 with those of reference lens Comparative Example 2 and lens 5 according to the present invention (similar structure except for the outermost LI layer / sheet). This Table 9 shows that Comparative Example 6 has a lower Rv and Ruv than both standard Comparative Example 2 and lens 5. Its σRv and colorimetric robustness (σh and σC* values) are very close to those of Comparative Example 2, but are worse than those of lens 5. In addition, the σRv of Comparative Example 6 and especially σRuv are greater than those of both standard Comparative Example 2 and lens 5. Therefore, its ESPF (considering 3σRuv) is almost the same as that of standard Comparative Example 2, but is significantly less than the ESPF of lens 5 according to the present invention.
[0325] D.8 Lenses 10 according to the present invention and comparative lens 7 (anti-reflection feature)
[0326] Table 10 below shows the structural and optical characteristics of reference lens comparative example 7 compared with lens 10 according to the present invention. Lens 10 has been obtained by replacing the standard SiO2 outermost layer (with a stable refractive index) with the outermost LI sheet layer according to the present invention, which includes three layers here: SiO2 + pQ25 + pQ50 and has a decreasing refractive index gradient in the direction away from the substrate.
[0327]
[0328] Table 10
[0329] Table 10 shows the layer structure of a conventional mirror coating (comparative lens 7) with a uniform outermost SiO2 layer. A new mirror for lens 10 has been obtained by replacing the outermost SiO2 layer with three sub-layers SiO2 + pQ25 + pQ50 according to the present invention. In the M coating of lens 10, the outermost SiO2 + pQ25 + pQ50 layer is a gradient decreasing refractive index layer. It is noted that the colorimetric robustness of the M coating is better than that of the reference conventional mirror stack with a uniform outermost SiO2 layer (with lower σh* and σC* values). In addition, σRv of the new M coating is also less than that of conventional comparative example 4.
[0330] D.9 Lenses 11 according to the present invention and comparative lens 8 (anti-reflection feature)
[0331] Table 11 below shows the structural and optical characteristics of reference lens comparative example 8 compared with lens 11 according to the present invention. Lens 11 has been obtained by replacing the standard SiO2 outermost layer (with a stable refractive index) with the outermost LI sheet layer according to the present invention, which includes three layers here: SiO2 + pQ25 + pQ50 and has a decreasing refractive index gradient in the direction away from the substrate.
[0332]
[0333] Table 11
[0334] Table 11 shows the layer structure of another conventional mirror coating with a uniform outermost SiO2 layer. A new mirror stack according to the present invention has been obtained by replacing the outermost SiO2 layer with three sub-layers SiO2 + pQ25 + pQ50. In lens 11, the outermost SiO2 + pQ25 + pQ50 layer is a gradient decreasing refractive index layer. The colorimetric robustness of the M coating of lens 11 is better than that of the reference conventional mirror stack with a uniform outermost SiO2 layer (with lower σh* and σC* values). Additionally, σRv of the new M coating of lens 11 is also less than that of the conventional reflective mirror stack.
[0335] D.10 Mechanical properties
[0336] In order to study the mechanical properties of the new AR coatings according to the present invention, some lenses have been prepared according to the structure shown in Table 12 below:
[0337]
[0338] Table 12
[0339] Lens 12 according to the present invention is coated with the new AR coating described for Lenses 1 and 5 having a gradient-decreasing refractive index outermost SiO2 layer. Comparative Examples 9 and 10 were prepared for comparison. Comparative Example 9 is coated with a standard AR coating on Cx and another standard AR coating on Cc. Comparative Example 10 is coated with the comparative AR coating described for Comparative Examples 5 and 6.
[0340] The parameters tested were as follows:
[0341] * The Tv coefficient, also known as the "light transmittance" of the system, is defined as in ISO standard 13666:1998 and is measured according to standard ISO 8980-3. It is defined as the average value in the wavelength range of 380 - 780 nm, which is weighted according to the sensitivity of the eye at each wavelength in this range and is measured under D65 lighting conditions (daylight).
[0342] * The critical temperature of the different lenses was measured in the manner specified in patent application WO 2008 / 001011. The critical temperature was measured one day, one week, and one month after the production of the articles.
[0343] * Before and after the tests, the haze value of the lenses tested was measured by light transmittance using a Haze-Guard Plus haze meter (color difference meter) from BYK-Gardner according to the method of ASTM D1003-00, as disclosed in WO 2012 / 173596. Since haze is a measure of the percentage of transmitted light scattered more than 2.5° from the axis of the incident light, the lower the haze value, the lower the degree of turbidity. Generally, for the lenses described herein, a haze value less than or equal to 0.3% is acceptable, and a haze value less than or equal to 0.2% is more preferred.
[0344] * Determination of abrasion resistance ("ISTM Bayer test" or "Bayer alumina")
[0345] As disclosed in WO 2012 / 173596, the abrasion resistance was determined. Specifically, one week after the production of the articles, the abrasion resistance was measured by the sand Bayer test according to the ASTM F735-81 standard.
[0346] *Evaluation of the adhesion characteristics of the coating (n*10 air-blowing test)
[0347] A qualitative test is carried out using a procedure called "nx10 air-blowing test". This procedure enables the evaluation of the adhesion of the film deposited on a substrate (such as an ophthalmic lens). The test is carried out as described in international patent application WO 99 / 49097. The operator checks the state of the lens being tested every 3 cycles by visual inspection. The number of cycles at which the defect first appears is noted. Thus, the higher the test value, the better the adhesion of the layers of the AR stack to the substrate. For comparison purposes, the nx10 air-blowing value of a standard anti-reflection glass is about 12. The n*10 air-blowing test results of some of the prepared lenses are reported in Table 14 (the test was carried out on 30 identical lenses).
[0348] The results are as follows:
[0349]
[0350] Table 13
[0351] It was found that all three lenses had no adhesion problems (N10>12). All the mechanical and thermal properties of lens 12 were very close to those of standard comparative example 9, indicating that replacing the outermost SiO2 layer with a gradient refractive index decreasing layer SiO2 + pQ25 + pQ50 does not sacrifice the mechanical properties of the AR coating. However, for comparative example 12, both the abrasion resistance (Taber) and heat resistance (critical temperature) were significantly reduced compared to the standard comparative example 10 lens. In addition, its haze level was also significantly increased.
Claims
1. An optical product, comprising at least: a base element having a front main surface and a rear main surface, and at least one interference multilayer coating, deposited onto the front and / or rear main surface of said base element and comprising at least one layer having a low refractive index of less than 1.55, defined as "LI layer", and at least one layer having a high refractive index equal to or greater than 1.55, defined as "HI layer", said refractive indices being expressed at a wavelength of 550 nm at 25° C., Features: The interference multilayer coating comprises an outermost layer which exhibits a refractive index gradient which decreases in a direction away from the base element and has a refractive index maximum value of less than 1.
55.
2. The optical product according to claim 1, wherein: The interference multilayer coating has, in reflection, a chromaticity C* as defined in the International Colorimetric CIE L*a*b* (1976) whose standard deviation, defined as "σC*", is strictly less than 2.0 for an angle of incidence of 15°, and a hue angle as defined in the International Colorimetric CIE L*a*b* (1976) whose standard deviation, defined as "σh", is less than or equal to 15° for an angle of incidence of 15°, provided that the interference multilayer coating has a mean light reflectance Rv in the visible region less than or equal to 2.5% for an angle of incidence of 15°, or Chromaticity C*, whose standard deviation, defined as "σC*", is strictly less than 6.9 for an angle of incidence of 15°, and has a hue angle, whose standard deviation, defined as "σh", is less than or equal to 5.8° for an angle of incidence of 15°, provided that the interference multilayer coating has an average light reflectance Rv in the visible light region strictly greater than 2.5% for an angle of incidence of 15°.
3. The optical product according to claim 2, wherein: The interference multilayer coating has, in reflection, - σC*, for an angle of incidence of 15°, is less than or equal to 1.9, provided that the interference multilayer coating has Rv≤2.5% for an angle of incidence of 15°, or σC*, for an angle of incidence of 15°, is less than or equal to 6.8, provided that the interference multilayer coating has an Rv>2.5% for an angle of incidence of 15°.
4. The optical product according to claim 3, wherein: - said σC* is less than or equal to 1.8 for an angle of incidence of 15°, provided that said interference multilayer coating has Rv≤2.5% for an angle of incidence of 15°, or The σC* is less than or equal to 6.7 for an angle of incidence of 15°, provided that the interference multilayer coating has an Rv>2.5% for an angle of incidence of 15°.
5. The optical product according to claim 4, wherein: - said σC* is less than or equal to 1.7 for an angle of incidence of 15°, provided that said interference multilayer coating has Rv≤2.5% for an angle of incidence of 15°, or The σC* is less than or equal to 6.6 for an angle of incidence of 15°, provided that the interference multilayer coating has an Rv>2.5% for an angle of incidence of 15°.
6. The optical product according to claim 2 or 3, wherein: The interference multilayer coating has, in reflection for an angle of incidence of 15°, the chromaticity C*, which is greater than or equal to 5, provided that the interference multilayer coating has an Rv≤2.5% for an angle of incidence of 15°, or the chromaticity C*, which is greater than or equal to 5, provided that the interference multilayer coating has an Rv>2.5% for an angle of incidence of 15°.
7. The optical product according to claim 6, wherein: the chromaticity C* is greater than or equal to 6, provided that the interference multilayer coating has an Rv≤2.5% for an angle of incidence of 15°, or The chromaticity C* is greater than or equal to 20, provided that the interference multilayer coating has an Rv>2.5% for an angle of incidence of 15°.
8. The optical product according to claim 7, wherein: the chromaticity C* is greater than or equal to 7, provided that the interference multilayer coating has an Rv≤2.5% for an angle of incidence of 15°, or The chromaticity C* is greater than or equal to 30, provided that the interference multilayer coating has an Rv>2.5% for an angle of incidence of 15°.
9. The optical product according to claim 2 or 3, wherein: The interference multilayer coating has, in reflection for an angle of incidence of 15°, - said σh, which is less than or equal to 11°, provided that said interference multilayer coating has Rv≤2.5% for an angle of incidence of 15°, or - said σh, which is less than or equal to 5.7%, provided that the interference multilayer coating has Rv>2.5% for an angle of incidence of 15°.
10. The optical product according to claim 1 or 2, wherein: The interference multilayer coating has an average light reflectance Rv in the visible light region of less than or equal to 2.5% for an incident angle of 15°.
11. The optical product according to claim 10, wherein: Rv is less than or equal to 2.0%.
12. The optical article according to claim 11, wherein: Rv is less than or equal to 1.5%.
13. The optical product according to claim 1 or 2, wherein: The interference multilayer coating has an average light reflectance Rv in the visible light region for an incident angle of 15°, and its standard deviation, defined as “σRv”, is less than or equal to 0.10%.
14. The optical article according to claim 13, wherein: σRv is less than or equal to 0.09%.
15. The optical article according to claim 14, wherein: σRv is less than or equal to 0.08%.
16. The optical product according to claim 1 or 2, wherein: The interference multilayer coating has an average reflection coefficient Ruv in the wavelength range of 280 nm to 380 nm of less than or equal to 5% for an angle of incidence of 35°.
17. The optical article according to claim 16, wherein: Ruv is less than or equal to 3.0%.
18. The optical article according to claim 17, wherein: Ruv is less than or equal to 2.5%.
19. The optical product according to claim 1 or 2, wherein: The interference multilayer coating has an average reflectance Ruv in the wavelength range of 280 nm to 380 nm for an incident angle of 35°, the standard deviation of the average reflectance, defined as “σ Ruv ”, being less than or equal to 0.50%.
20. The optical article according to claim 19, wherein: σRuv is less than or equal to 0.45%.
21. The optical article according to claim 21, wherein: σRuv is less than or equal to 0.40%.
22. The optical article according to claim 1 or 2, wherein: The outermost layer has a maximum refractive index less than or equal to 1.
52.
23. The optical article according to claim 22, wherein: The outermost layer has a maximum refractive index less than or equal to 1.
48.
24. The optical article according to claim 23, wherein: The outermost layer has a maximum refractive index less than or equal to 1.
47.
25. The optical article according to claim 1 or 2, wherein: The outermost layer: is deposited by evaporating at least one precursor compound using electron beam evaporation in a vacuum chamber with the introduction of oxygen, the flow rate of said oxygen being gradually increased during the deposition of said outermost layer, Optionally, the outermost layer comprises SiO2.
26. The optical article according to claim 1 or 2, wherein: The outermost layer has a physical thickness less than or equal to 150 nm.
27. The optical article according to claim 26, wherein: The outermost layer has a physical thickness less than or equal to 90 nm.
28. The optical article according to claim 1 or 2, wherein: The outermost layer is composed of a single layer or at least two layers or at least three layers.
29. The optical article according to claim 28, wherein: In a direction away from the base element, - the outermost layer is composed of a first layer and a second layer deposited on the first layer, the thickness of the first layer is less than or equal to 55 nm, and the thickness of the second layer is less than or equal to 55 nm; or -The outermost layer is composed of a first layer, a second layer deposited on the first layer, and a third layer deposited on the second layer, the thickness of the first layer is less than or equal to 50nm, the thickness of the second layer is less than or equal to 50nm, and the thickness of the third layer is less than or equal to 55nm.
30. A method for producing an optical article as claimed in any one of claims 1 to 29, comprising the steps of: (a) providing a base element having a front major surface and a rear major surface; (b) depositing the interference multilayer coating including the outermost layer onto the front major surface and / or the rear major surface in a vacuum chamber, wherein the outermost layer is deposited by evaporating at least one precursor compound using electron beam evaporation in the vacuum chamber with the introduction of oxygen, the flow rate of the oxygen being gradually increased during the deposition of the outermost layer.
31. The method according to claim 30, wherein: The precursor compound is silicon oxide, or a mixture of SiO2+Al2O3 (silicon dioxide doped with aluminum oxide).
Citation Information
Patent Citations
Process for producing plastic lens
EP0404111A2
Abrasion-resistant coating compositions containing hydrolised silanes and aluminium compounds; coated articles resistant to abrasion and shocks
EP0614957A1
Process for improving impact resistance of coated plastic substrates
EP0680492A1
Anti-smudge agent, method of forming an anti-smudge layer, anti-reflection optical member and display device
EP0933377A2
Plastic lens and its manufacture
JP1988087223A